Étude sur les besoins spécifiques des femmes immigrantes francophones en situation minoritaire - Alliance des femmes de la francophonie canadienne; Beaulieu, Denise (L’Alliance des femmes de la francophonie canadienne (AFFC), 2021)
Ce rapport présente les constats qui ressortent de l’étude sur les besoins spécifiques des femmes immigrantes francophones dans les communautés francophones en situation minoritaire (CFSM) de quatre provinces et un territoire (P/T) du Canada : Colombie-Britannique, Manitoba, Nouvelle-Écosse, Ontario et Yukon. Cette étude a été réalisée dans le cadre du projet Intégration des nouveaux arrivants dans les communautés francophones au pays, porté conjointement par l’Alliance des femmes de la francophonie canadienne (AFFC), la Commission nationale des parents francophones (CNPF) et la Fédération des aînées et aînés francophones du Canada (FAAFC). Son volet femmes a pour principal objectif de favoriser une meilleure compréhension des besoins des femmes immigrantes francophones au Canada. L’étude visait à identifier les besoins des immigrantes francophones ayant choisi de s’établir dans les quatre provinces et le territoire mentionnés ci-dessus, en lien avec les capacités des Réseaux d'immigration francophone et des services d’établissement à appuyer leurs efforts d’inclusion. Quelques recommandations portent sur les services de santé.

Stratégies d’intégration et de support en santé mentale des immigrants francophones au Canada anglais. - Archambault, Hélène; de Moissac, Daniel; Tempier, Raymond (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Cet article explore les stratégies d’intégration au système de santé telles que proposées par des personnes immigrantes francophones au sein de communautés francophones en situation minoritaire au Canada (CFSM). Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante personnes adultes immigrantes ou réfugiées. Centrées sur les représentations des personnes immigrantes quant aux services de soutien en santé mentale, diverses stratégies ont été dégagées. La préparation prémigratoire et le regroupement des informations sous un guichet unique semblent contribuer à une intégration réussie. L’appui des organismes communautaires et des autorités religieuses est bénéfique pour le soutien informationnel et socioémotionnel des nouveaux arrivants, ayant des retombées positives sur leur bien-être et leur capacité de s’intégrer à leur nouveau milieu de vie. Mots-clés : immigration, francophones, intégration, système de santé, stratégies Abstract This article explores healthcare integration strategies proposed by Francophone immigrants within Francophone minority communities (FMCs) in Canada. A qualitative study using semi-structured interviews was conducted in three Canadian cities with sixty adult immigrants and refugees. Focusing on immigrants’ perceptions of mental health support services, various strategies were identified. Pre-migration preparation and centralizing information seem to contribute to successful integration. The support of community organizations and religious authorities is beneficial for the socio-emotional and information support of newcomers, having a positive impact on their well-being and their ability to integrate into their new living environment. Keywords: immigration, Francophones, integration, healthcare, strategies

Expérience d'immigration de Francophones en contexte linguistique minoritaire au Canada : défis et répercussions sur la santé mentale - Archambault, Hélène; de Moissac, Danielle; Levesque, Annabel; Kinkumba, Babou; Gueye, Ndeye Rokhaya; Tempier, Raymond; Alimezelli, Hubert Tote (Reflets, 2021)
Résumé Cet article explore les défis rencontrés par de nouveaux arrivants francophones à leur arrivée dans une communauté francophone en situation minoritaire au Canada, les répercussions qui en découlent et les facteurs modérateurs ayant une incidence sur leur intégration. Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante adultes immigrants ou réfugiés. Le défi principal auquel sont confrontées ces personnes est la barrière linguistique ; elle vient amplifier les défis liés à l’intégration sociale et la recherche de l’emploi. L’expérience migratoire a aussi une répercussion sur la santé mentale, sur les relations avec les proches et sur la santé physique. Le soutien social et la résilience personnelle favorisent l’adaptation dans la communauté d’accueil. Mots-clés : immigration, francophones, intégration, contexte linguistique minoritaire Abstract This article explores challenges that Francophone newcomers face at their arrival in a francophone community in a minority context in Canada, as well as the impact of these obstacles on, and moderating factors associated to, the integration process. A qualitative research was conducted, using semi-structured interviews with sixty immigrants or refugees in three Canadian cities. The most challenging obstacle is the language barrier, as it has a direct impact on social integration and employment-seeking. The migration experience also has an impact on mental health, interpersonal relationships and physical health. Social support and personal resilience foster adaptation into the host community. Keywords: immigration, francophones, integration, linguistic minority context

Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.

Distance, access and equity: A cross-sectional geospatial analysis of disparities in acess to primary care for French-only speakers in Ottawa, Ontario - Belanger, Christopher; Carr, Kady; Peixoto, Cayden; Bjerre, Lise M. (CMAJ Open, 2023)
Background: Although language concordance between patients and primary care physicians results in better quality of care and health outcomes, little research has explored inequities in travel burden to access primary care people of linguistic minority groups in Canada. We sought to investigate the travel burden of language-concordant primary care among people who speak French but not English (French-only speakers) and the general public in Ottawa, Ontario, and any inequities in access across language groups and neighbourhood ruralities. Methods: Using a novel computational method, we estimated travel burden to language-concordant primary care for the general population and French-only speakers in Ottawa. We used language and population data from Statistics Canada’s 2016 Census, neighbourhood demographics from the Ottawa Neighbourhood Study, and collected the main practice location and language of primary care physicians from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Results: We included data from 869 primary care physicians and 916 855 patients. Overall, French-only speakers faced greater travel burdens than the general population to access language-concordant primary care. Median differences in travel burden were statistically significant but small (median difference in drive time 0.61 min, p < 0.001, interquartile range 0.26–1.17 min), but inequities in travel burden between groups were larger among people living in rural neighbourhoods. Interpretation: French-only speakers in Ottawa face modest — but statistically significant — overall inequities in travel burden when accessing primary care, compared with the general population, and higher inequities in specific neighbourhoods. Our results are of interest to policy-makers and health system planners, and our methods can be replicated and used as comparative benchmarks to quantify access disparities for other services and regions across Canada.

Patient and Provider Satisfaction With a Geomapping Tool for Finding Community Family Physicians in Ontario, Canada: Cross-Sectional Online Survey Study. - Belanger, Christopher; Peixoto, Cayden; Francoeur, Sara; Bjerre, Lise M. (JMIR formative research, 2024)
Background: Language-concordant health care, or health care in a patient’s language of choice, is an important element of health accessibility that improves patient safety and comfort and facilitates an increased quality of care. However, prior research has found that linguistic minorities often face higher travel burdens to access language-concordant care compared to the general population. Objective: This study intended to assess patient experiences and satisfaction with an online interactive physician map that allows patients to find family physicians who speak their preferred language in and around Ottawa, Ontario, Canada, as a means of identifying areas of improvement. Methods: This study used an online survey with questions related to user satisfaction. Responses to Likert-scale questions were compiled as summary statistics and short-answer responses underwent thematic analysis. The study setting was Ottawa and Renfrew County, Ontario, and the surrounding region, including the province of Quebec. Results: A total of 93 respondents completed the survey and self-identified as living in Ontario or Quebec. Overall, 57 (61%) respondents were “very satisfied” or “somewhat satisfied” with the map, 16 (17%) were “neither satisfied nor dissatisfied,” and 20 (22%) were “very dissatisfied” or “somewhat dissatisfied.” We found no significant differences in satisfaction by preferred language, age group, physician attachment, or intended beneficiary. A total of 56 respondents provided short-answer responses to an open-ended question about map improvements. The most common specific suggestion was to show which physicians are accepting new patients (n=20). Other suggestions included data refreshes (n=6), user interface adjustments (n=23), and additional languages (n=2). Some participants also provided positive feedback (n=5) or expressed concern with their inability to find a family physician (n=5). Several comments included multiple suggestions. Conclusions: While most patients were satisfied with the online map, a significant minority expressed dissatisfaction that the map did not show which family physicians were accepting new patients. This suggests that there may be public interest in an accessible database of which family physicians in Ontario are currently accepting new patients.

Going the distance: a cross-sectional geospatial analysis quantifying province-wide inequities in travel-based access, and fragility of access to French-language primary care provided by family physicians in Ontario, Canada - Belanger, Christopher; Timony, Patrick E; Bélizaire, Arlynn; Desilets, Antoine; Fitzsimon, Jonathan Peter; Gauthier, Alain P; Godfrey, Leanda; Karunananthan, Sathya; Kehoe MacLeod, Krystal; Muray, Mwali-Nachishali; Peixoto, Cayden; Bjerre, Lise M (BMJ Open, 2026)
Objectives Language-concordant care, or healthcare in one’s preferred language, is important both for health equity and for improving health outcomes. Linguistic minorities, like Francophones in Ontario, Canada, are at risk of poorer clinical outcomes if they receive non-language-concordant primary care. However, common ratio-based access measures can provide misleading views of minorities’ actual access levels. This cross-sectional geospatial study demonstrates a new way to measure primary care access using average travel time to the nearest five English- and French-speaking family physicians. We also introduce the concept of primary care access fragility, where a region’s primary care access may depend on one or a few local family physicians. Our research question is: are there differences in travel burden and access fragility for census subdivisions (CSDs) across language (English/French), rurality (urban/rural) and region (north/south) in the province of Ontario, Canada? Design We conducted a cross-sectional geospatial analysis to estimate English-language and French-language primary care travel burdens and access fragility in Ontario, Canada. We used population and boundary data from Statistics Canada’s 2021 census, road-network data from OpenStreetMaps, and family physician practice locations and language abilities from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Setting: We conducted our analysis for Ontario, Canada’s 577 CSDs, which correspond roughly to municipalities and with populations ranging from 5 inhabitants in Rainy Lake 17B to a high of 2 794 356 in Toronto. Participants: Using public data from January 2026, we identified 15 762 family physicians practising in Ontario, of whom 11.0% reported speaking French. Patient data were obtained from the most recent 2021 census. Primary and secondary outcome measures: Our first primary outcome measures were CSD-level mean travel time to the nearest five English-speaking family physicians, and CSD-level mean travel time to the nearest five French-speaking family physicians, which we compared to explore regional inequities in travel burden. Our secondary outcome measures were based on a novel notion of the travel burden component of ‘primary care access fragility’. This metric indicates how dependent a region’s access is on a small number of local physicians and is defined as the difference between the CSD-level mean travel time to the nearest one physician and to the nearest five physicians. As the difference in travel times grows, so too does access fragility. Results Median differences in French-language and English-language travel burdens were strongly significant across rurality, regions and overall (median difference 13.4 min, p<0.001, IQR 4.9–29.3 min), as was primary care access fragility (median difference 5.2 min, p<0.001, IQR 0.8–18.4), with larger travel burdens and fragilities in northern and rural communities. Conclusions Compared with the general public, Ontario’s French-speakers face higher travel burdens to language-concordant family physicians and higher access fragility, especially in rural and northern regions. Our results are of interest to policymakers and health-system planners, and our methods are applicable to other populations and regions.

Étude sur les populations âgées et l’accès aux soins de longue durée en français en Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)
Ce rapport présente une analyse de la demande et de l’offre de services de santé en français (SSF) dans le secteur des soins de longue durée (SLD) en Ontario. En nous appuyant sur des données publiques ainsi que sur des données administratives fournies par le ministère de la Santé de l’Ontario, le rapport examine : 1. la demande régionale de SSF, évaluée selon la population ontarienne âgée de 65 ans et plus et la population francophone de ce groupe d’âge ; 2. l’offre de SSF, mesurée par le nombre et le type de foyers présents dans chaque région, ainsi que par les compétences linguistiques en français de leur personnel.

Study of aging populations and access to French-language long-term care in Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)

Pratique # 24 : Communauté accueillante 2.0 et Formation Les Communautés de Pratique : une démarche collaborative pour accroître l’offre de services en français (Ontario) - Benoît, Josée; Dagnogo, Djenaba Sarah; Renaud, Alexandre (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2023)
Le recrutement, l’intégration et la rétention de la main-d’œuvre en santé ayant les compétences linguistiques vices en français constituent des défis importants auxquels font face un grand nombre d’organismes de santé. En 2014-2018, Communauté accueillante faisait partie d’un projet pilote pour favoriser le recrutement et la rétention de ressources humaines bilingues dans le domaine de la santé et des services sociaux dans le sud de l’Ontario. Ce projet a permis la création de cinq communautés de pratique qui pouvaient regrouper les professionnel·les bilingues d’agences de santé et services sociaux, des étudiant·es bilingues provenant des programmes de soins infirmiers, travail social, médecine, psychologie, orthophonie et autres programmes identifiés dans les régions, les collèges et universités francophones et anglophones qui offrent ces programmes partout en Ontario, ainsi que les professionnel·les bilingues de la santé et des services sociaux qui désirent être informé·es des ressources communautaires et opportunités de carrières dans ces régions. Les cinq communautés de pratique faisant partie du projet pilote Communauté accueillante 2.0 ont mis en place des stratégies et des activités qui leur sont propres, selon les besoins de leur région, permettant le partage de ressources, d’expertises, de connaissances et de pratiques innovantes inter-régions, mais également un partage de ressources entre paliers. Par exemple, des informations venant de la Société Santé en français ou de Santé Canada pouvaient facilement être distribuées entre les régions. En 2023, afin de diffuser les leçons tirées de ce projet, le Réseau franco-santé du Sud de l’Ontario a produit une ressource d’apprentissage intégrée à la Plateforme accès éQUITÉ dans le but d’appuyer le travail collaboratif mené en communautés de pratique pour concevoir des stratégies permettant d’accroître l’offre des services de santé en français dans les communautés francophones en situation minoritaire.

Portrait régional de la santé des aîné.es francophones et anglophones de l’Ontario: Résultats de l’Enquête sur la santé dans les collectivités canadiennes (ESCC), cycles combinés 2015-2020 - Bouchard, Louise; Batista, Ricardo; Duong, Patrick (Université d'Ottawa, 2024)
Ce rapport vise à dresser un portrait de santé de la population ontarienne âgée de 65 ans et plus selon le groupe de langue officielle et les sous-régions de la province — l’Est, le Nord et le Sud-Ouest — à partir des données de l’Enquête sur la santé dans les collectivités canadiennes (ESCC) de Statistique Canada. Il présente le profil sociodémographique des personnes aînées, leurs comportements et habitudes de vie, leurs problèmes de santé et limitations d’activités, ainsi que certains indicateurs relatifs à l’utilisation des services de santé. Source de données : Enquête sur la santé dans les collectivités canadiennes (ESCC), cycles bisannuels combinés 2015-2016; 2017-2018 et 2019-2020.

Santé de la population francophone et anglophone âgée de 65 ans et plus de l’Ontario [affiche] - Bouchard, Louise; Batista, Ricardo; Duong, Patrick; Sauvé-Schenk, Katrine; Lizotte, Mathieu (Colloque 103 – L’offre des services de santé dans les langues minoritaires, 92e Congrès de l’Acfas, 2025)

Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario, 2021)
L’Enquête sur la santé dans les collectivités canadiennes (ESCC)1 est une initiative de l'Institut canadien d'information sur la santé (ICIS), Statistique Canada et Santé Canada pour améliorer les systèmes d’information sur la santé et les rendre utiles à la planification de la santé. L’ESCC est une enquête transversale qui vise à recueillir des renseignements sur l'état de santé, l'utilisation des services de santé et les déterminants de la santé de la population canadienne. Elle est réalisée depuis 2001, auprès d'un grand échantillon de répondants et conçue pour fournir des estimations fiables à l'échelle des régions sociosanitaires du Canada. Le présent rapport vise, à partir des données de l’ESCC, à rendre compte de l’évolution d’indicateurs de conditions sociales, de mode de vie, d’états de santé et de bien-être et d’utilisation des services de la population ontarienne francophone en situation minoritaire comparativement à la population majoritaire anglophone.

Experiences and Perspectives of Caregivers of Francophone Older Adults Accessing Community Health Services in Toronto: an Exploratory Qualitative Study - Boyd, Elizabeth K.; Beogo, Idrissa; Liu, Barbara; Schneider, Fabien; Norris, Mireille (Canadian Geriatrics Journal, 2025)
Background Canada is a bilingual country; however, outside of Quebec, healthcare services are predominantly offered in English. With the increasing older adult population and stretched healthcare resources, Francophone older adults may face significant challenges in accessing care due to their linguistic minority status. This study explores the experiences of caregivers of Francophone older adults in the Greater Toronto Area (GTA). Methods Using a convenience sampling strategy, caregivers of patients who had undergone geriatric assessment at the Centre Francophone du Grand Toronto (CFGT) were recruited. Participants underwent 45-minute, semi-structured interviews and completed demographic questionnaires. Three independent reviewers conducted qualitative content analysis of the interview transcripts, using the socioecological model of health and NVivo12. Results Nine participants were primarily female (n=5), with age ranges of 40–49 (n=2), 50–59 (n=3), and 60+ (n=4). They originated from North America (n=5), Africa (n=3), and the Middle East (n=1); about half preferred English over French. Thematic analysis identified three key themes: 1) Barriers Accessing Health Care in the French Language; 2) The Need for Interpreter Support; 3) Importance of Comprehensive Francophone Community Services. Conclusions Despite the presence of organizations (e.g., CFGT), this study reveals a significant gap in French-language services for older adults in the GTA, leading to increased challenges for their caregivers. Due to linguistic barriers, caregivers must act as interpreters to mitigate the risks associated with miscommunication and potentially worse health outcomes. Addressing these issues requires increasing bilingual healthcare providers, enhancing funding for Francophone community services, and improving support systems (e.g., interpreters).

Instantané de recherche : l’avantage surprenant des jeunes francophones touchées par la dépression - CAMH-Evidence Exchange Network (2020)
Cet Instantané de recherche résume l’article intitulé « Les enjeux intersectionnels de la demande de services de santé mentale au Canada : La situation des jeunes femmes dépressives francophones », publié dans la Revue canadienne de service social en 2018.

La recherche en temps réel : projet ECHO pour francophones - Détermination des besoins des fournisseurs de services desservant les communautés franco-ontariennes afin de créer un programme de formation en français sur le traitement des dépendances - CAMH-Evidence Exchange Network (2023)

Research as it Happens : ECHO project for Francophones - Assessing the needs of service providers working with Franco-Ontarian communities to create a French-language, substance use management training program - CAMH-Evidence Exchange Network (2023)

L'offre active de services de santé mentale en français en Ontario et au Manitoba : les rôles clés des instruments et des outils - Cardinal, Linda; de Moissac, Danielle; Deschênes-Thériault, Guillaume (Administration publique du Canada / Canadian Public Administration, 2023)
Cet article présente les données d'un sondage réalisé en 2019 sur la connaissance des gestionnaires et des professionnels œuvrant dans le domaine de la santé mentale en Ontario et au Manitoba de leurs obligations linguistiques et des outils qui favorisent la pratique de l'offre active de services français. L'étude permet de souligner que plus les professionnels et les gestionnaires comprennent leurs obligations, tant en Ontario qu'au Manitoba, plus ils peuvent profiter des outils existants pour s'en acquitter. L'étude montre qu'il existe en effet un lien entre la connaissance des obligations et l'utilisation des outils pour faire de l'offre active de services de santé mentale en français. Elle permet aussi d'insister sur le rôle clé des outils pour faire de l'offre active de services en français.

Évaluer le potentiel de soins linguistiquement concordants pour les francophones de l’Ontario : une étude populationnelle transversale. - Carr, Kady; Batista Moliner, Ricardo; Fitzgerald, Michael; Lamontagne, Sophie; Bader Eddeen, Anan; Timony, Patrick E.; Bédard, Daniel; Gauthier, Alain; Prud’homme, Denis; Landry, Josette-Renée; Chomienne, Marie-Hélène; Denis-Leblanc, Manon; et al. (Minorités linguistiques et société, 2024)
Cette étude a utilisé les données sur les médecins, la facturation et le recensement de 2016 dont dispose l’ICES pour examiner l’accès potentiel à des médecins de famille francophones pour les francophones résidant dans 1 643 aires de diffusion agrégées (ADA) de l’Ontario. L’Ontario compte 550 280 francophones, soit 4,1 % de sa population. Nous avons identifié 8 199 médecins de famille, parmi lesquels 1 169 se sont autodéclarés francophones. Le ratio provincial global pour les francophones était de 2,12 médecins par 1 000 résidentes et résidents, comparativement à un ratio de 0,66 pour les anglophones. Dans les ADA où les francophones étaient majoritaires, le ratio pour les francophones était inférieur au ratio pour les anglophones (0,63 vs 2,02), alors que dans toutes les autres ADA, le ratio francophone était plus élevé (3,46 vs 0,62 dans les 83,4 % des ADA où les francophones représentaient >0 % à <5 % de la population). Huit ADA du Nord-Est et de l’Est de l’Ontario présentaient un déficit relatif important de médecins de famille francophones par rapport au ratio provincial. Ces résultats donnent un aperçu des régions qui pourraient bénéficier de programmes visant à éliminer les barrières linguistiques. Mots-clés : Concordance linguistique, médecins de famille, accès aux soins primaires, francophones, Ontario

Le moment Monfort dans la francophonie canadienne. - Charbonneau, François; Bock, Michel (Presses de l’Université d’Ottawa, 2024)

Perceptions des professionnels de la santé quant aux besoins oncologiques pédiatriques offerts en français à domicile : étude descriptive qualitative - Chartrand, Julie; Jibb, Lindsay; Grandmont, Camille; Hardy-Bélanger, Élisabeth; Cheng, Sara; Balasa, Rebecca; Johnston, Donna (Revue canadienne de soins infirmers en oncologie, 2022)

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Coup d’œil sur la recherche : Implantation d’un programme de formation à l’offre active de services en français auprès des futurs professionnels de la santé et des services sociaux dans une université canadienne. - Consortium national de formation en santé; van Kemenade, Solange (2022)

Coup d’œil sur la recherche : Qualité et sécurité des soins de longue durée en Ontario [infographie] - Consortium national de formation en santé; van Kemenade, Solange (2022)

Les Canadiens partiellement français sont susceptibles à une augmentation des facteurs de risque cardiovasculaire : une étude de cohorte rétrospective basée sur la population - Daccache, J.; Savoury, M.; Yam, Y.; Chow, B. J. M. (Annales de Cardiologie et d'Angéiologie, 2020)
Introduction Grâce à diverses recherches menées dans le passé, il a été démontré que le Québec est la province avec les taux d’infarctus aigü du myocarde (IAM) et la prévalence des facteurs de risque cardiovasculaire les plus élevés au Canada. Cette étude proposée effectuera une analyse rétrospective sur les populations caucasiennes, afin d’analyser les facteurs de risque cardiovasculaire dans les populations partiellement francophones par rapport aux Canadiens-Français et non-Français. En outre, nous analyserons de près les deux sexes des populations susmentionnées. Méthode Cette étude de cohorte rétrospective, basée sur la population, a été réalisée en utilisant le registre de l’ACTC de l’Institut de cardiologie de l’Université d’Ottawa (ICUO). Les participants sont des patients de race blanche de tout âge, qui sont venus à l’ICUO pour une angiographie par tomodensitométrie, entre 2006 et 2018, et qui ont donné leur consentement éclairé. SPSS a été utilisé pour comparer les différentes populations (Canadiens-Français [CF], Canadiens partiellement Français [CPF], et Canadiens non-Français [CNF]) et les différents sexes. Résultats La population des CPF ressemble plus à celle des FC, ayant une incidence plus élevée de facteurs de risque cardiovasculaire tels que le tabagisme, la dyslipidémie et le diabète de type 2. Interprétation Nos résultats suggèrent que les CPF, comme les CF, pourraient bénéficier d’une éducation plus intensive et de techniques de modification du mode de vie.

Management strategies to improve French language service coordination and continuity for official language Francophone seniors in Canada - de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Kubina, Lucy-Ann (Healthcare Management Forum, 2020)
Evidence suggests that language barriers present obstacles to healthcare access and quality for Francophone seniors in official language minority communities across Canada. Addressing language barriers and providing continuity is challenging, as French language services (FLSs) rely heavily on bilingual providers and the practice of active offer by all staff. This qualitative research used semi-structured group and individual interviews to explore mechanisms supporting FLS coordination and continuity in two Canadian provinces. Identification of the language variable in health records, virtual healthcare, and FLS directories are conducive to FLS continuity, but financial and resource limitations present major obstacles. Management strategies to facilitate continuity of FLS across health organizations are discussed.

Barriers in accessing HIV care for Francophone African, Caribbean and Black people living with HIV in Canada: A scoping review - Djiadeu, Pascal; Yusuf, Abban; Ongolo-Zogo, Clémence; Nguemo, Joseph; Odhiambo, Apondi J.; Mukandoli, Chantal; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2020)
Introduction In 2001, 50%–55% of French-speaking minority communities did not have access to health services in French in Canada. Although Canada is officially a bilingual country, reports indicate that many healthcare services offered in French in Anglophone provinces are insufficient or substandard, leading to healthcare discrepancies among Canada’s minority Francophone communities. Objectives The primary aim of this scoping systematic review was to identify existing gaps in HIV-care delivery to Francophone minorities living with HIV in Canada. Study design Scoping systematic review. Data sources Search for studies published between 1990 and November 2019 reporting on health and healthcare in Francophone populations in Canada. Nine databases were searched, including Medline, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, the National Health Service Economic Development Database, Global Health, PsychInfo, PubMed, Scopus and Web of Science. Study selection English or French language studies that include data on French-speaking people with HIV in an Anglophone majority Canadian province. Results The literature search resulted in 294 studies. A total of 230 studies were excluded after duplicates were removed. The full texts of 43 potentially relevant papers were retrieved for evaluation and data extraction. Forty-one studies were further excluded based on failure to meet the inclusion criteria leaving two qualitative studies that met our inclusion criteria. These two studies reported on barriers on access to specialised care by Francophone and highlighted difficulties experienced by healthcare professionals in providing quality healthcare to Francophone patients in Ontario and Manitoba. Conclusion The findings of this scoping systematic review highlight the need for more HIV research on linguistic minority communities and should inform health policymaking and HIV/AIDS community organisations in providing HIV care to Francophone immigrants and Canadians.

La téléconsultation : un levier pour rehausser l’accès aux services de santé en français pour les communautés francophones en situation minoritaire de l’Ontario - Dorion, Michelle; Giroux, Isabelle; Dionne, Éric (Reflets, 2026)
Les écrits démontrent que l’accessibilité aux services de santé en français est lacunaire chez les communautés francophones vivant en situation minoritaire (CFSM). Cette barrière linguistique est alarmante, car elle peut avoir des conséquences graves sur la qualité des soins et sur la sécurité des patientes et patients francophones. Face à cette réalité, la téléconsultation représente une solution technologique prometteuse permettant d’élargir l’offre des services de santé en français pour les CFSM. Ainsi, cet article présente un point de vue critique quant à l’utilisation de la téléconsultation en abordant les avantages et les limites qui lui sont associés. Les possibilités qu’offre ce dispositif pour rehausser les services de santé en français chez les CFSM seront également abordées en tenant compte des données recueillies auprès de patientes et patients ainsi que des prestataires de soins de santé francophones concernant leurs expériences avec l’utilisation de la téléconsultation à l’Hôpital Montfort, un centre hospitalier francophone en Ontario. Research shows that access to healthcare services in French is deficient in Francophone minority communities. This language barrier is alarming as it can have negative impacts on the quality and safety of care provided for Francophone patients. Faced with this reality, teleconsultation is a promising technological solution to enhance the offer of services in French for Francophone minority communities. Thus, this article presents a critical view on the use of teleconsultation by addressing its associated benefits and limitations. The possibilities this technology offers to enhance health services in French to Francophones living in a linguistic minority community will also be addressed by taking into account the experience with teleconsultation of French-speaking patients and healthcare providers at Montfort Hospital, a Francophone community hospital in Ontario.

Vers une amélioration de la prestation de services de santé pour les Franco-Ontariens - Doucet, Pascale-Anne. M.; Gorham, Robyn; Hunt, Elena (Journal de recherche interdisciplinaire, 2021)
Malgré le statut de dualité linguistique du Canada, la communauté francophone continue d’être laissée pour compte par les autorités du pays. Plus spécifiquement, l’étendue et l’accès restreints des services de santé offerts aux francophones en Ontario posent un grave danger pour cette population. Les établissements qui dispensent des services de santé continuent d’ignorer les politiques de soins existantes. Cette situation impose plusieurs actions au niveau fédéral, législatif et communautaire nécessaires afin d’assurer la garantie bilingue promise à la population canadienne. Parmi celles-ci, il faut augmenter la présence francophone dans les groupes décisionnels pour assurer la conception et l’établissement de programmes et services de santé axés sur les besoins uniques et distincts des franco-ontariens. Par ailleurs, l’engagement financier fédéral envers des organismes communautaires francophones est essentiel afin de fournir plus de services de santé en français, surtout dans les communautés nordiques et rurales de la province. Finalement, la subvention gouvernementale de futures recherches sur la santé des francophones est nécessaire puisque celles-ci vont servir de base solide pour déterminer comment mieux desservir cette population. Pour y arriver, il faudrait considérer le lobbying, l’encouragement des institutions qui dispensent des services de santé d’obtenir leur désignation bilingue, et la mise à jour de la Loi sur les services en français. Cependant, en continuant l’inaction, les Franco-Ontariens risquent de devenir assimilés au restant de la population, de dépérir et de voir leur santé se détériorer. Cet article cherche notamment à signaler la nécessité d’améliorer la prestation de services de santé en français en Ontario.

L'obligation de communiquer en anglais dans les communautés francophones en contexte minoritaire: des futures infirmières issues de l'immigration témoignent de leur expérience en stage. - Duchesne, Claire; Déri, Catherine E.; Benoît, Josée (Minorités linguistiques et sociétés/Linguistic Minorities and Society, 2023)
L’intégration socioprofessionnelle des infirmières de langue française issues de l’immigration est particulièrement souhaitée par les membres des communautés francophones situées dans les provinces et territoires où la langue de la majorité est l’anglais et où les francophones éprouvent de la difficulté à se faire soigner dans leur langue de préférence. Cet article propose une contextualisation des enjeux de l’immigration dans les communautés francophones en contexte minoritaire et, notamment, du besoin d’accueillir des professionnels de langue française dans ces communautés. Des entretiens de recherche réalisés auprès de quatre stagiaires infirmières francophones issues de l’immigration feront état des défis linguistiques qu’elles ont rencontrés dans leurs milieux de stage, particulièrement au regard de la langue anglaise. Enfin, des pistes de solution pour soutenir l’intégration socioprofessionnelle de ces futures infirmières seront également proposées. Mots-clés : infirmières issues de l’immigration, intégration socioprofessionnelle, communautés francophones en contexte minoritaire, formation et stages

Multimorbidity: Exploring determinants and differences between Francophones and Anglophones in Ontario - Duong, Patrick; Batista, Ricardo; Lizotte, Mathieu; Sauvé-Schenk, Katrine; Bouchard, Louise (2024)

La multimorbidité : prévalence et déterminants chez les francophones et les anglophones de l’Ontario [affiche] - Duong, Patrick; Lizotte, Mathieu; Batista, Ricardo; Sauvé-Schenk, Katrine; Bouchard, Louise (Colloque 103 – L’offre des services de santé dans les langues minoritaires, dans le cadre du 92e Congrès de l’Acfas, 2025)

Visualisation des données sur l’offre et la demande de services en soins de longue durée en Ontario: un portrait régional de de l'offre et des besoins réalisé à l'aide de la plateforme dynamique Power-BI de Microsoft (version 2025) - Duong, Patrick; Timony, Patrick E.; Belanger, Christopher; Glaude, Normand; Pelbois, Christelle; Bouchard, Louise (Forces-Santé, 2026)

Visualization of data on the supply and demand for French-language long-term care services in Ontario: A regional snapshot of French-language long-term care supply and demand in Ontario,created using Microsoft's dynamic Power-BI platform (version 2025) - Duong, Patrick; Timony, Patrick E.; Belanger, Christopher; Glaude, Normand; Pelbois, Christelle; Bouchard, Louise (Forces-Santé, 2026)

Tableaux de bord : L’offre et la demande de services de santé en français - Soins de longue durée. (Power-BI, version bêta) - Duong, Patrick; Timony, Patrick E.; Glaude, Normand; Bouchard, Louise (Forces-Santé - Vitrine de données, 2026)
Résumé Ce tableau de bord propose une visualition interactive des données afin d'illustrer le potentiel de l'analyse géographique et de mieux compremdre les besoins des communautés francophones de l'Ontario en matière de soins de longue durée, dans une perspective d'équité et d'accès aux services. Abstract This dashboard provides an interactive visualization of data to illustrate the potential of geographic analysis and to better understand the long-term care needs of Ontario's Francophone communities, with a focus on equity and access to services.

Overview of French-Language Health Services in Ontario (2017–2020): Infographic of a study conducted by Ozi. - Forces-Santé (2025)

Portrait des services de santé en français en Ontario (2017–2020): Infographie d'une étude menée par Ozi - Forces-Santé (2025)

Analyse des retombées des fonds de recherche du CNFS - Volet université d'Ottawa, période 2013-2020 - Forest, Mariève (Consortium national de formation en santé - Volet Université d'Ottawa, 2020)

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)

Insertion professionnelle dans le domaine de la santé des personnes immigrantes francophones vivant en situation minoritaire - Forest, Mariève; Goss Gilroy Inc (Ministère Immigration, Réfugiés et Citoyenneté Canada, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Monfort dans la jurisprudence. - Foucher, Pierre (Le moment Monfort dans la francophonie canadienne, 2024)

Les services en français en Ontario en mal de géographie - Gilbert, Anne (Droits, langues et communautés, 2023)

Apprentissage de l’offre active des services sociaux et de santé en français par module de simulation interprofessionnelle au bénéfice des francophones en situation minoritaire au Canada - Giroux, Isabelle; Savard, Jacinthe; Tyerman, Jane; Savard, Sébastien; Benoît, Josée; Kengneson, Cris-Carelle (Revista de Llengua i Dret, 2025)
Résumé La formation des futurs prestataires de soins à l’offre active (OA) des services sociaux et de santé (SSS) en français est essentielle pour permettre l’accès équitable à des services de qualité pour les francophones en situation minoritaire (FSM) au Canada. L’apprentissage par module de simulation interprofessionnelle est une avenue prometteuse à évaluer. L’objectif du présent travail est d’évaluer la satisfaction et l’efficacité perçue de l’apprentissage de l’OA des SSS en français à l’aide d’un module de simulation interprofessionnelle spécifique, le MODULE-IP-SIM-OA. En ce qui concerne la méthodologie, des stagiaires de programmes en SSS de l’Université d’Ottawa ont complété le dit module, suivi d’un débreffage synchrone et d’un questionnaire de rétroaction en ligne, entre mai et décembre 2023. Les 216 stagiaires issus de neuf disciplines ont rapporté des taux élevés de satisfaction et d’efficacité perçue concernant le MODULE-IP-SIM-OA et son débreffage. Cet apprentissage, jugé efficace par les stagiaires, pourrait avoir des retombées positives sur l’offre de services aux FSM afin d’atténuer les barrières linguistiques en santé. Resum La formació dels futurs professionals de la salut sobre l’oferta activa (OA) dels serveis socials i de salut (SSS) en francès és essencial per permetre un accés equitatiu a serveis de qualitat a les persones francòfones en situació minoritària (FSM) al Canadà. L’aprenentatge mitjançant un mòdul de simulació interprofessional és una via prometedora que cal explorar. L’objectiu d’aquest treball és avaluar el nivell de satisfacció i d’eficàcia percebuda de l’aprenentatge de l’OA dels SSS en francès amb l’ajuda d’un mòdul de simulació interprofessional específic, el MODULE-IP-SIM-OA. Pel que fa a la metodologia, diversos estudiants en pràctiques de programes de SSS de la Universitat d’Ottawa van completar aquest mòdul, seguit d’una sessió de debrífing síncrona i d’un qüestionari de valoració en línia, entre els mesos de maig i desembre de 2023. Els 216 estudiants, provinents de nou disciplines diferents, van aportar respostes que indiquen nivells alts de satisfacció i d’eficàcia percebuda en relació amb el MODULE-IP-SIM-OA i el debrífing posterior. Aquest aprenentatge, que els participants van considerar eficaç, podria tenir efectes positius en l’oferta de serveis als FSM per reduir les barreres lingüístiques en l’àmbit de la salut. Abstract Training future care providers in the active offer (AO) of social and health services (SHS) in French is essential for ensuring equitable access to quality services for Francophones in minority contexts (FMS) in Canada. Learning through an interprofessional simulation module is a promising approach that warrants evaluation. The purpose of this paper is to assess the satisfaction and perceived effectiveness of learning the AO of SHS in French using a specific interprofessional simulation module, the MODULE-IP-SIM-OA. Regarding methodology, between May and December 2023, trainees from SHS programs at the University of Ottawa completed this module, followed by a synchronous debriefing and an online feedback questionnaire. The 216 trainees from nine disciplines reported high levels of satisfaction and perceived effectiveness regarding the MODULE-IP-SIM-OA and its debriefing. This learning experience, considered effective by the trainees, could have positive impacts on service delivery to FMS and help reduce language barriers in healthcare. Resumen La formación de los futuros profesionales de la salud sobre la oferta activa (OA) de los servicios sociales y de salud (SSS) en francés es esencial para permitir un acceso equitativo a servicios de calidad a las personas francófonas en situación minoritaria (FSM) en Canadá. El aprendizaje mediante un módulo de simulación interprofesional es una vía prometedora que hay que explorar. El objetivo de este trabajo es evaluar el nivel de satisfacción y de eficacia percibida del aprendizaje de la OA de los SSS en francés con la ayuda de un módulo de simulación interprofesional específico, el MODULE-IP-SIM-OA. Con respecto a la metodología, varios estudiantes en prácticas de programas de SSS de la Universidad de Ottawa completaron este módulo, seguido de una sesión de debriefing síncrona y de un cuestionario de valoración en línea, entre los meses de mayo y diciembre de 2023. Los 216 estudiantes, provenientes de nueve disciplinas diferentes, aportaron respuestas que indican niveles altos de satisfacción y de eficacia percibida en relación con el MODULE-IP-SIM-OA y el debriefing posterior. Este aprendizaje, que los participantes consideraron eficaz, podría tener efectos positivos en la oferta de servicios a los FSM para reducir las barreras lingüísticas en el ámbito de la salud.

Occupational Integration in Healthcare by French-speaking Immigrants Living in Minority Communities - Goss Gilroy Inc. (GGI) (2020)
This report presents the results of a research project on the occupational integration of French speaking immigrants in healthcare, in Francophone minority communities. Through interviews, this project examines the challenges faced by French-speaking immigrants working or pursuing a career in the health sector in Nova Scotia, Ontario and Alberta. Researchers also mobilized literature on the occupational integration of immigrants, data from the 2016 Census and the results of quantitative studies. The research shows that the need for English language skills constitutes a major obstacle at various stages of French-speaking immigrants’ occupational integration journey. The interviews also indicate that employment assistance services in French are not equipped to deal with the complex trajectories of internationally educated health professionals, or to help them identify alternative careers. During internships or at the start of employment, supports in French promoting the integration of immigrants (through mentoring, training workshops for employers, etc.) are very limited. Recommendations are addressed to the Department of Immigration, Refugees and Citizenship Canada and aim to improve supports offered to the study population from the start of their migration project to retention in their workplace.

La francophonie ontarienne en 2021 - Gouvernement de l'Ontario (2021)

L’usage de technologies de santé pour accéder à des soins virtuels : une enquête exploratoire pour mieux comprendre les besoins et attentes des francophones de l’Ontario - Grosjean, Sylvie; Giguère, Lauriane; Lessard, Lysanne; Dionne, Émilie (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons les résultats d’une étude visant à répondre à la question suivante : quels usages des technologies numériques de santé sont jugés accessibles et acceptables par les francophones de l’Ontario? Les résultats de cette enquête exploratoire montrent que l’accessibilité et l’acceptabilité des technologies de santé pour soutenir l’offre de soins virtuels chez les francophones de l’Ontario dépendent de plusieurs facteurs liés : a) à leur utilité perçue, b) à leur valeur sociale et leur intégration dans des usages existants, et c) à l’offre des technologies accessibles en français – de leur conception au support offert pour en accompagner les usages. Les résultats de l’étude nous invitent à considérer les questions à la fois communicationnelles (concordance linguistique patient/technologie), organisationnelles (intégration dans des pratiques et structures existantes) et éthiques qu’implique l’usage des technologies de santé visant à soutenir l’offre de soins virtuels pour les francophones de l’Ontario. Mots-clés : soins virtuels, technologies numériques de santé, acceptabilité, francophones, Ontario

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)
Au début de la pandémie, un relâchement des obligations linguistiques dans les institutions publiques et les gouvernements a été observé (Chouinard & Normand, 2020). Ceci a pu avoir un impact sur les proches aidants et les bénéficiaires de soins en situation linguistique minoritaire. Notre équipe a voulu documenter le vécu de personnes proches aidantes en réalisant une étude à méthodologie mixte sur l’impact de la pandémie de la COVID-19 sur les personnes proches aidantes de personnes aînées et sur la relation aidant-aidé. Les résultats détaillés sont présentés dans l'article : Savard J. et al. (2026). Prolonged impact of the COVID-19 Pandemic... Nous avons choisi de synthétiser le vécu des proches aidants vivant en situation linguistique minoritaire par des récits inspirés des témoignages recueillies dans cette étude. Le récit suivant a été formulé à partir d'entretiens individuels auprès de quatre proches aidantes provenant de trois provinces canadiennes, dont la personne aînée recevant les soins demeurait dans un domicile privé.

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)
Au début de la pandémie, un relâchement des obligations linguistiques dans les institutions publiques et les gouvernements a été observé (Chouinard & Normand, 2020). Ceci a pu avoir un impact sur les personnes proches aidantes et les bénéficiaires de soins en situation linguistique minoritaire. Notre équipe a voulu documenter le vécu de proches aidants en réalisant une étude à méthodologie mixte sur l’impact de la pandémie de la COVID-19 sur les personnes proches aidantes de personnes aînées et sur la relation aidant-aidé. Les résultats détaillés sont présentés dans l'article : Savard J. et al. (2026). Prolonged impact of the COVID-19 Pandemic... Nous avons choisi de synthétiser le vécu des personnes proches aidantes vivant en situation linguistique minoritaire par des récits inspirés des témoignages recueillis dans cette étude. Le récit suivant a été formulé à partir d'entretiens individuels auprès de quatre proches aidantes provenant de deux provinces canadiennes, dont la personne aînée recevant les soins demeurait dans une maison de retraite pour personnes autonomes ou semi-autonomes.

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Practice # 28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (2025)

Pratique # 28: Accès aux ressources communautaires (ARC) : Un modèle de prescription sociale et de navigation (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2025)
Bien qu'il existe de nombreux services et programmes communautaires destinés à répondre aux besoins sociaux et de santé de la population, beaucoup de patients, patientes et médecins généralistes ignorent leur existence, ou peinent à s'y retrouver dnas la multitudes programmes existant. Le modèle ARC est intégré aux soins primaires afin d'aider les patient·es à accéder aux ressources disponibles pour répondre à leurs besoins sociaux et de santé non satisfaits. Cette approche prévoit un point d'entrée unique pour les besoins en santé (non médicaux) et sociaux, amène des changements dans les pratiques afin d'aider les prestataires de soins primaires à mobiliser leur patientèle dans la prise en charge autonome de ces besoins, et fait appel aux services d’un·e navigateur·trice communautaire non clinique, chargé d’accompagner les patient·es dans l’accès aux ressources communautaires appropriées. Parmi les caractéristiques du modèle, on retrouve un acompagnement linguistique bilingue : Les navigateurs et navigatrices ARC sont formés pour offrir un soutien linguistique en français et en anglais pour répondre aux besoins des patient·es, adoptent une approche d’« offre active » et veillent à ce que les patient·es puissent accéder facilement et confortablement aux services et à l’information dans la langue de leur choix.

Recrutement de prestataires de services maîtrisant le français : conseils et stratégies - Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (2023)
Le présent rapport a été conçu en tant que ressource pour aider l’"Équipe santé Enfants avant tout" à élaborer une stratégie de recrutement, de maintien en poste et de formation des ressources humaines dans la région sanitaire de Champlain, en Ontario. Le rapport a été préparé par l’Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (« l’Institut du savoir »). L’Institut du savoir crée des liens, transmet des connaissances et tire parti de son expertise pour améliorer les compétences des prestataires de services directs et des organismes de l’Ontario afin de renforcer les programmes et les services de santé mentale de l’Ontario pour tous les enfants, les jeunes, les familles et les prestataires de soins. Nous voulions savoir ce que font les organismes — particulièrement ceux du secteur de la santé — pour recruter des prestataires de services qui maîtrisent le français. Nous voulions aussi nous renseigner sur les pratiques de recrutement fondées sur des données probantes décrites dans la littérature. Les stratégies et les principes directeurs présentés dans cette ressource sont tirés d’une analyse contextuelle qui comprenait un examen rapide et non systématique de la littérature. De plus, nous avons consulté des intervenant.e.s clés et des leaders dans le domaine qui ont une expérience directe de recrutement de prestataires de services qui maîtrisent le français.

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

Les effets potentiels de la version française du NCLEX-RN® sur le choix de la langue de formation d'étudiantes infirmières francophones en situation minoritaire. - Lalonde, Michelle; Chartrand, Julie; Vanderspank- Wright, Brandi; McGillis Hall, Linda; Gosselin-Bélanger, Amélie; Fullum, Jessica Adèle (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2020)
Abstract Background: Since the introduction of the new entry to practice exam, the NCLEX-RN®, there has been a very low success rate among Francophone nursing students living in minority situations. In addition, there has been a drop in the number of candidates who choose to write the exam in French. These results are of great concern in terms of the quality and sustainability of French language health services in French language minority communities in Canada. Objectives: The purpose of this article is to present the results of a study exploring the experiences of students enrolled in an entry level nursing program in French in terms of their decision-making regarding: 1) the choice of the language of the nursing program in which they were enrolled, 2) the language in which they chose to write the NCLEX-RN®, 3) their interest in working in a Francophone context, 4) their general knowledge of the new entry to practice exam, and 5) information sources on the NCLEX-RN©. Methodology: A sequential mixed methods design using surveys with multiple-choice and open-ended questions was used to conduct this study. Descriptive analyzes, as well thematic and content analysis, were used to analyze the data. Results: 51 students from a francophone graduating cohort participated in this study. The majority of the participants expected to write the NCLEX-RN® in English; the media attention on the French version of the exam influenced their decision. Four main themes were highlighted : 1) Choice of language of student based on their first language, 2) Three main factors that influence the choice of the language in which they write the NCLEX-RN®, 3) Colleagues and media as sources of information on the NCLEX-RN®, and 4) Importance and pride of studying in French. Conclusion: The results of this project shed light on the factors that influence francophone students' decision-making regarding the choice of language for the exam and the reasons why graduating students would choose to study in French again or not. Résumé Contexte : Un très faible taux de réussite a été remarqué chez les étudiantes infirmières francophones en situation minoritaire ainsi qu’une chute du nombre de candidates qui choisissent de passer en français le nouvel examen d’autorisation, le NCLEX-RN®, qui a été introduit en 2015. Ces données sont préoccupantes s’agissant de la qualité et de la pérennité des services de santé en français dans les régions linguistiques minoritaires au Canada. Objectifs : Le but de cet article est de présenter les résultats concernant les expériences des étudiantes inscrites dans un programme de formation initiale en sciences infirmières en français sur leur prise de décision quant à : 1) la langue du programme auquel elles se sont inscrites, 2) la langue dans laquelle elles ont choisi de passer le NCLEX-RN®, 3) leur intérêt à travailler dans un contexte francophone, 4) leurs connaissances générales relatives au nouvel examen d’autorisation et 5) les sources d’information sur le NCLEX-RN®. Méthodologie : Un devis de recherche mixte séquentiel a été retenu comportant l’utilisation de questionnaires. Des analyses descriptives et des analyses thématiques et de contenu ont été effectuées. Résultats : 51 étudiantes de la cohorte francophone ont participé à cette étude. La majorité des participantes comptaient passer le NCLEX-RN® en anglais; l’intérêt médiatique porté à la version française de l’examen a eu une influence sur leur décision. Quatre grands thèmes ont été mis en évidence à partir des questions à court développement du questionnaire : 1) langue maternelle choisie comme langue de formation, 2) trois principaux facteurs qui influencent le choix de la langue pour le NCLEX-RN®, 3) collègues et médias comme sources d’information sur le NCLEX-RN®, et 4) importance et fierté d'étudier en français. Conclusion : Les résultats de ce projet ont mis en évidence les facteurs qui influencent la prise de décision des étudiants francophones quant au choix de la langue de l’examen et les raisons pour lesquelles les finissantes étudieraient à nouveau en français.

Expérience des étudiants francophones issus d’immigrations récentes lors de leur première année d’étude en sciences infirmières - Larocque, Sylvie; Lavoie, Anne. Marise; Muray, Kalum; Waja, Chamberline (Revue de la Diversité de la Recherche en Santé, 2021)

La première étape de la validation transculturelle des versions anglophones des tests de l'horloge et du Mini-Mental pour mesurer les capacités cognitives des Franco-Ontariens âgés de plus de 65 ans - Larocque, Sylvie; Lavoie, Anne-Marise; Omri, Nadia (Reflets, 2021)
La maladie d’Alzheimer est un syndrome neurodégénératif chronique caractérisé par un déclin cognitif et mnésique. Les personnes atteintes par cette maladie développent des affections rattachées à la langue. Il est important de faire passer des tests de dépistage dans la langue maternelle de la personne puisque l’aptitude linguistique décline avec la progression de la maladie. De manière générale, le Mini-mental et le test de l’horloge sont administrés en anglais aux francophones du nord de l’Ontario ce qui peut mener à une sous-évaluation de leurs capacités cognitives et à un diagnostic erroné. Voilà pourquoi le but de cette recherche était de développer et valider les tests psychométriques francophones administrés aux Franco-Ontariens. Le Mini-mental et le test de l’horloge ont été traduits selon la validation transculturelle de Caron (1999) et testés auprès des francophones du Grand Sudbury qui souffraient de déficits cognitifs (N=14). Aucune différence statistique (p>.05) entre les scores de la traduction franco-ontarienne du test de l’horloge et du Mini-mental comparés aux tests originaux n’a été détectée. Bien que d’autres recherches soient nécessaires, selon les auteures, ces traductions permettront d’assurer un dépistage juste de cette maladie chez les francophones âgés en situation minoritaire. Mots-clés : dépistage d’Alzheimer, Mini-mental de Folstein, test de l’horloge, traduction transculturelle

Évaluation des besoins de santé et intégration à la culture francophone, anglophone et autochtone chez les enfants métis en milieu minoritaire - LeBlanc, Angèle; Roy-Charland, Annie; Paquette, Tara; Boulard Poirier, Jessica; Young, Nancy. L. (Enfance en difficulté, 2021)
Ce projet a pour objectif d’adapter et de traduire un questionnaire lié à la santé et au bien-être des enfants métis : la Mesure de la santé et du bien-être des enfants métis (MSBEM), en plus de déterminer si les enfants métis de la communauté du Grand Sudbury sont davantage intégrés à la culture autochtone, francophone ou anglophone. Mots-clés : Métis, intégration culturelle, minorité, besoins de santé, autorapport

Exploring Primary Care Physicians’ Experiences of Language and Cultural Discordant Care for Linguistic Minority Patients at the End-of-Life: A Study Protocol - Lee, Seung Heyck; Gibb, Maya; Karunananthan, Sathya; Cody, Margaret; Tanuseputro, Peter; Johnston, Sharon; Kendall, Claire; Bedard, Daniel; Collin, Stéphanie; Kehoe MacLeod, Krystal (International Journal of Qualitative Methods, 2023)
Health disparities exist across different linguistic groups. Language barriers in primary care can negatively affect access to healthcare services and the quality and safety of care at the end-of-life. This study will take a novel, in-depth look at the experience of language- and/or cultural-discordant care for adults from linguistic minority groups through the eyes of primary care physicians providing palliative and/or end-of-life care. Language and cultural discordance means that the physician and patient do not speak the same language or are not from the same cultural background. Qualitative data from primary care physicians (n = 12–24) providing language-discordant end-of-life care to Francophone and/or Allophone older adults across different care models and diverse geographies in Ontario will be collected through semi-structured interviews. Reflexive thematic analysis will be used to report themes within the data and consider the influence of the social locations of the researcher and research participants, geographic considerations impacting service provision, and barriers imposed by differing primary care funding structures on the provision of palliative and end-of-life care for linguistic and cultural minority groups in Ontario. Findings from this study will identify the interconnections among language and cultural discordance, care model, geographic region, and physician perceptions of their combined effects on access to, and quality of, palliative and end-of-life care. This evidence will be key to informing clinical practice guidelines and mobilizing change to improve primary care access and quality for adults at the end-of-life from linguistic and cultural minority populations across Ontario. Keywords: language discordance, qualitative research, reflexive thematic analysis, palliative care, primary care physicians, semi-structured interviews

Dans l’oeil de la tempête : la Commission de restructuration des services de santé de l’Ontario et l’Hôpital Montfort, 1996-1997 - Martel, Marcel (Le moment Monfort dans la francophonie canadienne, 2024)

L’expérience d’un échec à l’examen professionnel infirmier NCLEX-RN des diplômées d’un programme ontarien francophone de Baccalauréat en sciences infirmières - McGee, Shannon; Larocque, Sylvie; Pilon, Roger (Diversity of Research in Health Journal / Revue de la diversité de la recherche en santé, 2023)
Résumé En 2015, l’examen canadien d’admission à la profession infirmière a changé de format et est devenu similaire à celui des États-Unis. Les premiers résultats canadiens à l’examen d’admission NCLEX-RN ont démontré de nombreux échecs, qui touchaient davantage les francophones. Le but de la recherche était de décrire l’expérience de cet échec par des diplômées d’un baccalauréat ontarien en sciences infirmières francophone. Un devis qualitatif de type phénoménologique a été retenu comportant des entrevues individuelles semi-dirigées. La méthode d’analyse de Giorgi a été effectuée. Les résultats ont démontré que les participantes francophones ont vécu des difficultés supplémentaires peu importe la langue choisie qui, entre autres, a résulté à un ou plusieurs échecs de cet examen. L’impact d’un échec est dévastateur pour ces candidates et a des répercussions négatives sur les programmes de sciences infirmières francophones ainsi que sur l’accès au service de santé en français. Mots-clés :NCLEX-RN, examen d’autorisation, sciences infirmières, francophone, échec. Abstract In 2015, the Canadian nursing licensing exam changed its format and became similar to that of the United States. Initial results for the Canadian NCLEX-RN licensing exam demonstrated numerous failures, with Francophones failing at a greater rate. The aim of this study was to describe the experience of the NCLEX-RN exam failure by French-speaking Bachelor of Science Nursinggraduates of an Ontario program. A qualitative phenomenological design was chosen, comprising semi-structured individual interviews. Analysis of all interviews was completed using the Giorgi method. Results demonstratedthat French-speaking participants experienced additional difficulties regardless ofif they wrote the exam in French or English and were also more likely to experience one or more failures of this exam. The impact of failure has been described as devastating by participants of the study. Furthermore, the failure rates have had negative repercussions on Francophone nursing programs and can negatively impact access to healthcare services in French. KeyWords: NCLEX-RN, Nursing, Francophone, Fail, Licensing exam

Accès aux soins de longue durée dans la région d'Érié St. clair : Analyse et recommandation - Mian, Guy (Entité de planification des services de santé en français Érié St.Clair/Sud-Ouest, 2021)
Ce rapport a été préparé dans le cadre du Plan d’Action Conjoint 2019-2022 du RLISS-Entité,¹ où les soins et les services aux aînés sont considérés comme prioritaires et, en particulier, l’accès aux soins de longue durée (SLD) dans la région d’Érié St. Clair. Le présent rapport vise à formuler des recommandations à l’intention de Santé Ontario (SO) Ouest afin de combler les lacunes en matière d’accessibilité aux soins de longue durée (SLD) en français et, par conséquent, dans les services de soutien à domicile et en milieu communautaires (SSDMC) afin de maintenir les aînés francophones à domicile dans la région d’Érié St. Clair (ESC). Dans la mesure du possible, le rapport proposera également des recommandations pour la localité de London dans la région du Sud-Ouest (S-O).

Montfort fermé : jamais? Le discours nationalitaire de SOS Montfort dans les journaux franco-ontariens - Miville, Serge (Recherches sociographiques, 2021)
Cet article cherche à comprendre l’impact des stratégies discursives utilisées par SOS Montfort dans l’espace médiatique franco-ontarien durant la crise entourant la fermeture de l’hôpital Montfort entre 1997 et 2002. En analysant les principaux journaux régionaux de langue française de la province, l’auteur évalue la capacité mobilisatrice du discours nationalitaire que génèrent les défenseurs de l’hôpital à travers le prisme des régionalismes en Ontario français. Alors que SOS Montfort tente de faire de la fermeture de l’hôpital une crise provinciale et nationale, les Franco-Ontariens d’autres régions doivent, de leur côté, composer avec la réelle possibilité de perdre l’accès à des soins de santé en français en raison du processus de rationalisation des services de santé à l’échelle de la province. Si SOS Montfort a réussi à faire de la fermeture de Montfort une crise importante en Ontario français en puisant dans l’imaginaire référentiel franco-ontarien, son incapacité d’inclure les enjeux d’ordre régionaux dans son discours a limité sa force de frappe à l’extérieur d’Ottawa où l’hôpital n’offre aucun service. This article seeks to understand the impact of the discursive strategies used by the SOS Montfort coalition in the Franco-Ontarian media space during the crisis surrounding the closure of the Montfort Hospital between 1997 and 2002. By analyzing the province’s main French-language regional newspapers, the author evaluates the mobilizing capacity of the nationalist discourse generated by the hospital’s defenders through the prism of regionalisms in French Ontario. While SOS Montfort attempts to turn the hospital closure into a provincial and national crisis, Franco-Ontarians in other regions must deal with the real possibility of losing access to French-language health care as a result of the province-wide health services rationalization process. While SOS Montfort has succeeded in carving out the closure of Montfort as a major crisis in French Ontario, namely by tapping into the Franco-Ontarian referential imaginary, its inability to include regional issues in its discourse has limited its impact outside of Ottawa, where the hospital offers no services.

Official Language Minority Communities in Ontario: Understanding the Lived Experiences of Francophone Patients and their Nursing Care Providers - Muray, Mwali (Université d'Ottawa/University of Ottawa, 2022)
Although Canada is a bilingual country, official language minority community patients struggle to access quality care in their language. This reality has been of concern for Francophone minority communities in Ontario, but has seldom been examined in a nursing context. This research sought to examine the lived experiences of registered nurses and nursing students providing care to French-speaking patients in Ontario, as well as the realities of Francophone patients seeking French language health care services in Ontario. The conceptual frameworks guiding the study were the “Four Levels of Change for Improving Quality” model and the “Four-Level Model of the Health Care System.” Using qualitative phenomenological inquiry, as influenced by Martin Heidegger and Max van Manen, 31 semi-structured interviews were conducted with three subsets (n=10 Francophone patients; n=10 nursing students; n=11 registered nurses) throughout Ontario who had experience with the phenomenon being investigated. Data collection took place over a year (2018-2019) and was analysed thematically. Significant findings were identified across the three groups. Participants revealed the patchwork of individual actions taking place to remedy the existing gaps regarding care for Francophone minority populations. This included navigating a health care system where good enough care was the unfortunate standard for Francophone patients, and discussing how Francophone patients and nursing care providers implement strategies individually to manage the lack of resources for Francophone patient populations in Ontario. This thesis asserts that official language minority communities and their nursing care providers remain faced with difficulties providing and receiving care in Ontario. While numerous structures and resources exist to remediate the problems, these interventions and resources are not always implemented systemically, leading to a disproportionate burden on individuals, significant risks for safety for patient populations, and ethical dilemmas for nursing care providers. Recommendations are provided to bridge the gaps and ensure considerations of the needs of linguistic minorities throughout the health care system. Keywords: Francophonie, Linguistic Minorities, Nursing, Phenomenology, Qualitative Research

Official Language Minority Communities in Ontario: (In)visibility of Nursing Care - Muray, Mwali; Chartrand, Julie; Perron, Amélie (Aporia, 2026)
Despite Canada’s linguistic duality, French-speaking minority populations continue to face significant barriers in accessing equitable health care. Investigating two key research questions, this study explores: (1) What are the lived experiences of registered nurses and nursing students caring for French-speaking patients in Ontario? and (2) How do French-speaking patients navigate the health care system to access care in their preferred language? Using qualitative methodology informed by interpretive phenomenology, 31 participants were interviewed individually between 2018 and 2019, offering firsthand accounts of their experiences. Findings reveal a paradox of (in)visibility: French-speaking patients and nursing providers remain invisible when they adapt to systemic shortcomings but become highly visible when they advocate for equitable care. The study highlights the urgent need for the effective and consistent implementation of the strategic changes within health care institutions. Addressing these linguistic disparities is not only a matter of patient safety and quality care but also a fundamental step toward upholding Canada’s bilingual commitments in health service delivery.

(Re)penser le travail social avec et pour la communauté des adultes autistes francophones de l’Ontario au prisme de la neurodiversité et de l’intersectionnalité : quand les savoirs d’expérience s’entremêlent - Nugent, Bianca (University d'Ottawa, 2026)
Située au croisement des études critiques en autisme, des approches afroféministes intersectionnelles et du travail social en contexte francominoritaire, cette thèse doctorale documente les inégalités sociales complexes (Collins & Bilge, 2016; Nash, 2017) vécues par les adultes autistes francophones en contexte minoritaire ontarien — une population largement absente des écrits scientifiques. Alors que les travaux récents dans le domaine des études critiques en autisme (Freeman Loftis, 2023 ; Milton et Ryan, 2022 ; Woods et Waldock, 2021 ; Gillespie-Lynch et al., 2017; O’Dell et al., 2016 ; Davidson et Orsini, 2013) exposent les injustices épistémiques et la neuronormativité (Catala et al., 2021 ; Claveau, 2024 ; Fricker, 2007), peu d’études francophones ont exploré ces phénomènes hors Québec. Mobilisant une approche intersectionnelle intracatégorielle (Nash, 2008 ; McCall, 2005), ainsi que les savoirs d’expérience autistiques (Catala, 2025 ; Botha et al., 2024 ; Kapp, 2020 ; Yergeau, 2017 ; Milton, 2014), cette recherche critique adopte une posture éthique et inclusive avec et pour les adultes autistes en recherche centrée sur les communautés (Cascio et al., 2020 ; Raymaker, 2016 ; Raymaker et Nicolaidis, 2013). Elle repose sur une méthodologie qualitative multimodale (sondages, autoentrevues, entretiens semi-dirigés et une rencontre de groupe) menée en Ontario auprès de vingt-quatre participant·e·s : douze adultes autistes ; six proches aidantes, dont cinq mères et une sœur d’un jeune adulte autiste ; six intervenant·e·s des domaines sociaux et communautaires francophones de l’Ontario. Au regard de l’offre active des services en français et de l’intervention sociale en contexte linguistique minoritaire (Reaume et al., 2024 ; Savard et al., 2024 ; Benoît et van Kemenade, 2017 ; Savard et al., 2015 ; Drolet et al., 2010), la thèse postule que les adultes autistes francophones de l’Ontario sont en situation de « surminorisation autistique francominoritaire ». Ce phénomène renvoie à l’invisibilisation sociale, linguistique et épistémique, lors que les personnes autistes francominoritaires se retrouvent exclues par les cadres anglonormatifs de l’autisme et brimées de leurs droits de minorités linguistiques (Forgues et Maillet, 2024 ; Baril, 2017a) devant des services en français généralistes peu adaptés à leur neurodivergence. Les résultats révèlent leurs parcours marqués par le désalignement et la rareté des services et des ressources en français en Ontario conjugué au manque de reconnaissance des réalités distinctes et des obstacles d’accès accrus pour les personnes autistes racisées, migrantes, de la pluralité de genre et de la diversité sexuelle ou résidant hors des grands centres. Leurs savoirs expérientiels recueillis ont permis de formuler des leviers d’action pour transformer les pratiques en travail social ; renforcer l’offre active de services et des ressources ; et informer les politiques publiques dans une perspective intersectionnelle, plurilinguistique et inclusive en contexte linguistique minoritaire. Cette thèse contribue au bassin émergent des études critiques canadiennes en autisme à l’âge adulte à l’intersection de langue, de l’identité, du genre, du statut socioéconomique et d’autres inégalités structurelles observées en contexte francominoritaire. Elle offre des fondements empiriques et théoriques pour une refonte des interventions sociales fondée sur la reconnaissance, l’autodétermination et la légitimation neuroaffirmative des voix des personnes autistes francominoritaires surminorisées.

Le programme de télésanté de prévention des chutes Marche vers le Futur : développement et retombées d’une communauté de pratique franco-canadienne - O’Neil, Jennifer; Dionne, Nathalie; Cardinal, Dominique; Savard, Jacinthe (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
Résumé Le programme de télésanté Marche Vers le Futur (MVF) a eu un impact positif sur le bien-être des personnes âgées francophones et sur leur accès aux services de prévention des chutes au Canada. L’objectif de ce projet était de développer et de mettre en place une communauté de pratique (CdP) facilitant le partenariat et le partage des connaissances entre les animateurs du programme MVF. La création de cette CdP a permis à vingt-deux animateurs de cinq provinces de partager des stratégies de recrutement, de promotion du programme et de sensibilisation quant aux besoins des personnes âgées francophones au pays. Quatre rencontres virtuelles ont permis d’identifier les obstacles à la pérennité de MFV, les facteurs facilitant la mobilisation des connaissances ainsi que les initiatives de formation continue. La CdP a permis de renforcer les réseaux de partenariat entre les chercheurs et les animateurs du programme MVF, ce qui pourrait avoir un impact important sur l’équité en santé chez les personnes âgées francophones vivant en situation minoritaire au Canada. Abstract Marche vers le Futur (MVF) is a telehealth program that has demonstrated a positive impact on the access to fall prevention services in Canada and the wellness of older Francophone adults living in minority situations. This project aimed to develop and implement a community of practice (CoP) to facilitate partnership and knowledge-sharing between MVF program facilitators across francophone communities in Canada. The creation of this CoP enabled twenty-two facilitators from five provinces to share strategies for recruiting, promoting, and sustaining the program as well as continuing to raise awareness around the importance of health prevention services tailored for older Francophone adults in Canada. Four virtual meetings were held to identify sustainability barriers, knowledge mobilisation facilitators, and continuing education initiatives. The CoP allowed to strengthen the partnership between researchers and program facilitators across diverse provinces which could impact health equity among older Francophone adults living in minority communities in Canada.

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Access to a telehealth falls prevention program: Mixed-method analysis from a health equity perspective - O’Neil, Jennifer; Dionne, Nathalie; Sauve-Schenk, Katrine; Savard, Jacinthe (Journal of Telemedicine and Telecare, 2026)
Introduction Access to falls prevention programs, addressing an important public health concern, is often limited for Francophone and Acadian minority communities. Technology has been used to deliver falls prevention programs, but health equity factors linked to improving its access for all are still poorly understood. This study aimed to document health equity factors influencing access from the perspective of older francophone adults in various communities across Canada. Methods Guided by the digital health equity framework, we used a sequential explanatory mixed method, including a descriptive sociodemographic questionnaire and semi-structured interviews, to document perspectives on access of persons who had completed different versions of a telehealth falls prevention program. Results Sixty-one participants from five provinces completed the sociodemographic questionnaire, of which most participants (n= 45) represented perspectives from francophone communities living in a minority situation. Results revealed that 91% of participants had access to a computer or tablet with adequate audio-visual components for telehealth. Twenty of these participants, from four provinces, shared their perspectives. The majority of them reported that falls prevention programs should be offered in their preferred language and with different delivery options that consider the social and safety preferences of participants. Eight recommendations informing policy and implementation emerged. Discussion Advocacy around digital connectivity is essential to ensure that all Canadians have equitable access to high-speed internet connections and proper infrastructure. Participants also raised the importance of adapting services to their linguistic realities, geographic location, safety, and basic needs to optimize the impact of the health services provided to them.

The new Inclusive definition of Francophone (IDF) - Office of Francophone Affairs (2020)

Problèmes d’accès aux services en français ? Contactez-nous. Nous pouvons vous aider [infographie] - Ombudsman de l'Ontario (2022)

2023-2024 Annual Report of the French Language Services Commissioner of Ontario. - Ombudsman Ontario (2024)

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)

Problems accessing services in French? Contact us. We can help [infographie] - Ontario Ombudsman (2022)

The impact of language on emergency department visits, hospitalizations, and lenght of stay among home care recipients - Reaume, M.; Batista, Ricardo; Rhodes, Emily; Knight, Braden; Imsirovic, Haris; Seale, Emily; Riad, Karine; Prud'homme, Denis; Tanuseputro, Peter (Medical care, 2021)
Background: Research considering the impact of language on health care utilization is limited. We conducted a population-based study to: (1) investigate the association between residents’ preferred language and hospital-based health care utilization; and (2) determine whether this association is modified by dementia, a condition which can exacerbate communication barriers. Methods: We used administrative databases to establish a retrospective cohort study of home care recipients (2015–2017) in Ontario, Canada, where the predominant language is English. Residents’ preferred language (obtained from in-person home care assessments) was coded as English (Anglophones), French (Francophones), or other (Allophones). Diagnoses of dementia were ascertained with a previously validated algorithm. We identified all emergency department (ED) visits and hospitalizations within 1 year. Results: Compared with Anglophones, Allophones had lower annual rates of ED visits (1.3 vs. 1.8; P<0.01) and hospitalizations (0.6 vs. 0.7; P<0.01), while Francophones had longer hospital stays (9.1 vs. 7.6 d per admission; P<0.01). After adjusting for potential confounders, Francophones and Allophones were less likely to visit the ED or be hospitalized than Anglophones. We found evidence of synergism between language and dementia; the average length of stay for Francophones with dementia was 25% (95% confidence interval: 1.10–1.39) longer when compared with Anglophones without dementia. Conclusions: Residents whose preferred language was not English were less frequent users of hospital-based health care services, a finding that is likely attributable to cultural factors. Francophones with dementia experienced the longest stays in hospital. This may be related to the geographic distribution of Francophones (predominantly in rural areas) or to suboptimal patient-provider communication.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.

Qualité et sécurité des services de santé offerts en situation linguistique minoritaire en Ontario : investigations des données administratives de santé. - Reaume, Michael; Batista, Ricardo; Prud’homme, Denis; Tanuseputro, Peter (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Dans cet article, nous présentons une synthèse de plusieurs analyses récentes réalisées par notre groupe de recherche à partir de données administratives de santé pour mesurer la qualité et la sécurité des services de santé offerts aux francophones et allophones en Ontario, Canada. Les résultats de nos analyses démontrent que les Ontariennes et les Ontariens qui reçoivent des soins dans leur principale langue d’usage ont généralement de meilleurs résultats cliniques comparés à ceux qui reçoivent des soins dans une langue autre que leur principale langue d’usage. Ceci suggère que la qualité et la sécurité des soins offerts aux patients et aux patientes en situation de discordance linguistique pourraient être améliorées par le pairage de professionnel-patient parlant la même langue, par exemple, en référant un patient à un médecin qui parle la langue du patient, ou en s’assurant que les francophones ont accès aux services en français en milieux désignés en Ontario en vertu de la Loi sur les services en français et que les allophones puissent bénéficier de davantage de services d’interprétariat. Mots-clés : allophones, données administratives de santé, francophones, minorités de langue officielle, minorités linguistiques, qualité et sécurité des soins de santé

Impact of patient–family physician language concordance on healthcare utilisation and mortality: A retrospective cohort study of home care recipients in Ontario, Canada. - Reaume, Michael; Batista, Ricardo; Sucha, Ewa; Pugliese, Michael; Roberts, Rhiannon; Rhodes, Emily; Seale, Emily; Kendall, Claire. E.; Bjerre, Lise; Bouchard, Louise; Johnson, Sharon; Sood, Manish; et al. (BMJ Public Health, 2024)
Introduction As the world’s linguistic diversity continues to increase at an unprecedented rate, a growing proportion of patients will be at risk of experiencing language barriers in primary care settings. We sought to examine whether patient–family physician language concordance in a primary care setting is associated with lower rates of hospital-based healthcare utilisation and mortality. Methods We conducted a population-based retrospective cohort study of 497 227 home care recipients living in Ontario, Canada. Patient language was obtained from home care assessments while physician language was obtained from the College of Physicians and Surgeons of Ontario. We defined primary care as language concordant when patients and their rostered family physicians shared a mutually intelligible language, and we defined all other primary care as language discordant. The primary outcomes were Emergency Department (ED) visits, hospitalisations and death within 1 year of index home care assessment. Results Compared with non-English, non-French speakers who received language-discordant primary care, those who received language-concordant primary care experienced fewer ED visits (53.1% vs 57.5%; p<0.01), fewer hospitalisations (35.0% vs 37.6%; p<0.01) and less mortality (14.4% vs 16.6%; p<0.01) during the study period. In multivariable regression analyses, non-English, non-French speakers had lower risks of ED visits (adjusted hazard ratio [aHR] 0.91, 95% CI 0.88 to 0.94), hospitalisations (aHR 0.94, 95% CI 0.90 to 0.98) and death (aHR 0.87, 95% CI 0.82 to 0.93) when they received language-concordant primary care. For francophones, the risk of experiencing an ED visit, a hospitalisation or death was not impacted by the language of their family physician. Conclusions Patient–family physician language concordance is associated with a lower risk of adverse outcomes in non-English and non-French speakers. Optimising the delivery of language-concordant care could potentially result in significant decreases in the use of acute healthcare services and mortality at the population level.

In-hospital patient harm across linguistic groups: A retrospective cohort study of home care recipients - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Guerin, Eva; Rhodes, Emily; Carson, Sarah; Prud'homme, Denis; Tanuseputro, Peter (Journal of patient safety, 2022)
Objective Research examining the impact of language barriers on patient safety is limited. We conducted a population-based study to determine whether patients whose primary language is not English are more likely to experience harm when admitted to hospitals in Ontario, Canada. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2010 to 2015) who were subsequently admitted to hospital. Patient language (obtained from home care assessments) was coded as English, French, or other. Harmful events were identified using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results We included 190,724 patients (156,186 Anglophones, 5,110 Francophones, and 29,428 Allophones). There was no significant difference in the unadjusted risk of harm for Francophones compared with Anglophones (relative risk [RR], 0.94; 95% confidence interval [CI], 0.87–1.02). However, Allophones were more likely to experience harm when compared with Anglophones (RR, 1.14; 95% CI, 1.10–1.18). The risk of harm was even greater for Allophones with low English proficiency (RR, 1.18; 95% CI, 1.13–1.24). After adjusting for potential confounders, Anglophones and Allophones were equally likely to experience harm of any type, but Allophones more likely to experience harm from infections and procedures. Conclusions Patients whose primary language was not English or French were more likely to experience harm after admission to hospital, especially if they had low English proficiency. For these patients, the risk of harm from infections and procedures persisted in the adjusted analysis, but the overall risk of harm did not.

The impact of hospital language on the rate of in-hospital harm. A retrospective cohort study of home care recipients in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Rhodes, Emily; Guerin, Eva; Carson, Sarah; Prud’homme, Denis; Tanuseputro, Peter (BMC Health Services Research, 2020)
Background Patients who live in minority language situations are generally more likely to experience poor health outcomes, including harmful events. The delivery of healthcare services in a language-concordant environment has been shown to mitigate the risk of poor health outcomes related to chronic disease management in primary care. However, data assessing the impact of language-concordance on the risk of in-hospital harm are lacking. We conducted a population-based study to determine whether admission to a language-discordant hospital is a risk factor for in-hospital harm. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2007 to 2015) who were admitted to a hospital in Eastern or North-Eastern Ontario, Canada. Patient language (obtained from home care assessments) was coded as English (Anglophone group), French (Francophone group), or other (Allophone group); hospital language (English or bilingual) was obtained using language designation status according to the French Language Services Act. We identified in-hospital harmful events using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results The proportion of hospitalizations with at least 1 harmful event was greater for Allophones (7.63%) than for Anglophones (6.29%, p <  0.001) and Francophones (6.15%, p <  0.001). Overall, Allophones admitted to hospitals required by law to provide services in both French and English (bilingual hospitals) had the highest rate of harm (9.16%), while Francophones admitted to these same hospitals had the lowest rate of harm (5.93%). In the unadjusted analysis, Francophones were less likely to experience harm in bilingual hospitals than in hospitals that were not required by law to provide services in French (English-speaking hospitals) (RR = 0.88, p = 0.048); the opposite was true for Anglophones and Allophones, who were more likely to experience harm in bilingual hospitals (RR = 1.17, p <  0.001 and RR = 1.41, p <  0.001, respectively). The risk of harm was not significant in the adjusted analysis. Conclusions Home care recipients residing in Eastern and North-Eastern Ontario were more likely to experience harm in language-discordant hospitals, but the risk of harm did not persist after adjusting for confounding variables.

The impact of patient-facility language discordance on potentially inappropriate prescribing of antipsychotics in long-term care home in Ontario, Canada: A retrospective population health cohort study - Reaume, Michael; Peixoto, Cayden; Pugliese, Michael; Tanuseputro, Peter; Batista, Ricardo; Kendall, Claire. E.; Landry, Josette-Renée; Prud’homme, Denis; Chomienne, Marie-Hélène; Farrell, Barbara; Bjerre, Lise M. (BMC Geriatrics, 2024)
Background Appropriate use of medication is a key indicator of the quality of care provided in long-term care (LTC). The objective of this study was to determine whether resident-facility language concordance/discordance is associated with the odds of potentially inappropriate prescribing of antipsychotics (PIP-AP) in LTC. Methods We conducted a population-based, retrospective cohort study of LTC residents in Ontario, Canada from 2010 to 2019. We obtained resident language from standardized resident assessments, and derived facility language by determining the proportion of residents belonging to each linguistic group within individual LTC homes. Using linked administrative databases, we identified all instances of PIP-AP during a 1-year follow-up period. PIP-AP was defined using the STOPP-START criteria, which have previously been shown to predict adverse clinical events such as emergency department (ED) visits and hospitalizations. The association between linguistic factors and PIP-AP was assessed using adjusted multivariable logistic regression analysis. Results We identified 198,729 LTC residents consisting of 162,814 Anglophones (81.9%), 6,230 Francophones (3.1%), and 29,685 Allophones (14.9%). The odds of PIP-AP of were higher for both Francophones (aOR 1.15, 95% CI 1.08–1.23) and Allophones (aOR 1.11, 95% CI 1.08–1.15) when compared to Anglophones. When compared to English LTC homes, French LTC homes had greater odds of PIP-AP (aOR 1.12, 95% CI 1.05–1.20), while Allophone homes had lower odds of PIP-AP (aOR 0.82, 95% CI 0.77–0.86). Residents living in language-discordant LTC homes had higher odds of PIP-AP when compared to LTC residents living in language-concordant LTC homes (aOR 1.07, 95% CI 1.04–1.10). Conclusion This study identified linguistic factors related to the odds of PIP-AP in LTC, suggesting that the linguistic environment may have an impact on the quality of care provided to residents.

La population francophone au sein de votre équipe Santé Ontario : proposition d’indicateurs clés - Réseau des services de santé en français de l'Est de l'Ontario (2022)

Le Réseau à l’écoute. Rapport à la communauté 2022-2023. - Réseau des services de santé en français de l’Est de l’Ontario (2024)
Le Réseau des services de santé en français de l’Est de l’Ontario (RSSFE ou Le Réseau) a lancé la nouvelle initiative Le Réseau à l’écoute en février 2022 auprès des membres du Réseau et de la communauté francophone de l’Est et du Sud-Est de l’Ontario. Il s’agit d’un espace privilégié pour entendre les expériences, tant positives que négatives, qu’ont les membres de la communauté francophone avec le système de santé. Ce premier rapport à la communauté sur Le Réseau à l’écoute couvre une période de 14 mois, portent sur 26 témoignages (représentent 51 expériences distinctes) reçus entre les mois de février 2022 et la fin de mars 2023.

Le Réseau à l’écoute. Rapport à la communauté 2023-2024. - Réseau des services de santé en français de l’Est de l’Ontario (2024)
Le Réseau des services de santé en français de l’Est de l’Ontario (RSSFE ou Le Réseau) a lancé l'initiative Le Réseau à l’écoute en février 2022 auprès des membres du Réseau et de la communauté francophone de l’Est et du Sud-Est de l’Ontario. Il s’agit d’un espace privilégié pour entendre les expériences, tant positives que négatives, qu’ont les membres de la communauté francophone avec le système de santé. Ce 2e rapport fait état de la collecte des données de l’année 2023-2024, au cours de laquelle Réseau à l'écoute a reçu 35 témoignages qui représentent 57 expériences uniques. En deux ans, Le Réseau à l’écoute a reçu 61 témoignages qui représentent 108 expériences uniques, dont une croissance de 35% du nombre de répondants dans la dernière année. Les expériences obtenues grâce au Réseau à l’écoute mettent en valeur la réalité de l’accès aux services de santé en français de même que les défis auxquels sont confrontés la communauté francophone lorsqu’il s’agit de recevoir des services de santé dans sa langueé

Mémoire sur la santé numérique en français en Ontario. Examen des documents d'orientation stratégique - Réseau des services de santé en français de l'Est de l'Ontario (2021)

Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire - Réseau des services de santé en français de l’Est de l’Ontario (2020)

Rapport provincial sur les SSEF (données de 2018-2019) - Réseau des services de santé en français de l'Est de l'Ontario; Institut Ozi (2020)
Le projet OZi a pour objectif de colliger et d’analyser des données afin de dresser un portrait de la capacité de SSEF. Cette initiative cherche à pallier le manque de données normalisées afin de permettre une planification efficace et une prise des décisions éclairée. Grâce au portail OZi, les fournisseurs de services de santé (FSS) financés par les RLISS ont fourni des données de référence sur leur capacité en matière de SSEF. Le présent rapport porte sur la deuxième année de collecte de données (année 2018-2019). L’analyse porte sur quatre perspectives : la répartition des FSS, le continuum des services, la conformité en matière de désignation et les ressources humaines.

Rapport provincial sur les SSEF (données de 2019-2020) - Réseau des services de santé en français de l'Est de l'Ontario; Institut Ozi (2021)
Le projet OZi a pour objectif de colliger et d’analyser des données afin de dresser un portrait de la capacité de SSEF. Cette initiative cherche à pallier le manque de données normalisées afin de permettre une planification efficace et une prise des décisions éclairée. Grâce à l'utilisation du portail OZi, des données sur la capacité à offrir des SSEF ont été recueillies auprès des fournisseurs de services de santé (FSS) financés par les RLISS. Ce rapport couvre la troisième année de collecte de ces données (2019-2020). L’analyse porte sur quatre perspectives : la répartition des FSS, la couverture du continuum des soins, la conformité aux exigences de désignation et les ressources humaines.

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Amélioration de l’expérience des francophones dans les soins de santé – Rapport final - Réseau du mieux-être francophone du Nord de l'Ontario (2021)
En 2018, le Réseau du mieux-être francophone du Nord de l’Ontario (Réseau) a obtenu des fonds afin de mener un projet portant sur l’expérience des francophones et, plus précisément, sur son amélioration en matière de services de santé en français dans la région du Nord de l’Ontario. Dans le contexte du projet, nous avons recueilli des expériences de patients francophones dans le but de valider les besoins qui ont souvent été identifiés par les francophones sur l’accès et l’équité des services de santé en français. Ces données nous ont permis de créer des ressources pour mieux outiller les fournisseurs de services de santé dans l'offre de soins culturellement adaptés. Ce document consiste en un sommaire des résultats obtenus à la suite des rencontres et des échanges avec des francophones de différentes régions du Nord de l’Ontario ainsi que des pistes de solution, des outils et des ressources pour appuyer les fournisseurs de services de santé à améliorer l’offre active de services de santé en français.

Boîte à outils virtuelle de soins culturellement adaptés pour les francophones dans les foyers de SLD - Réseau du mieux-être francophone du Nord de l’Ontario (2022)

État des lieux pour le secteur de la santé mentale et de lutte contre les dépendances dans le Nord de l'Ontario - Réseau du mieux-être francophone du Nord de l'Ontario (2025)
Le Réseau a entrepris le travail de recenser les capacités actuelles du secteur de la santé mentale et de lutte contre les dépendances, dans le Nord de l’Ontario, et ce, afin de mieux appuyer les organismes de soins de santé et ainsi renforcer les capacités du secteur. En effet, cette étude permettra au Réseau de connaitre les capacités actuelles en matière de professionnels de la santé qui parlent le français dans le Nord de l’Ontario, puis d’identifier les domaines et les régions où les disparités sont plus importantes, afin de guider le travail du Réseau auprès des diverses instances provinciales et des fournisseurs des services de santé. Ce rapport pourra également servir de guide envers l’établissement des priorités et de stratégies régionales en matière de services en français pour le secteur de la santé mentale et de lutte contre les dépendances. La majorité des données utilisées pour la réalisation de ce rapport sont tirées du rapport annuel 2022-2023 sur les services de santé en français envoyé au ministère de la Santé et Santé Ontario, rapport qui est rempli annuellement par tous les fournisseurs de services de santé (FSS) qui ont une entente avec Santé Ontario Nord. Les fournisseurs pour les populations autochtones sont toutefois exclus de cette étude. Afin d’analyser les capacités actuelles du système de santé dans le Nord de l’Ontario, le Réseau a choisi d’explorer quatre thématiques pour chacune des régions. Ces quatre thématiques sont la capacité en ressources humaines en français, l’offre active, la capture de l’identité linguistique et la documentation et les communications. Le Nord de l’Ontario peut être divisé en deux grandes régions, soit le Nord-Est et le Nord-Ouest. Chacune de ces grandes régions peuvent ensuite être divisées de nouveau en quatre régions, soit les régions de l’Algoma, de Cochrane, de Nipissing-Temiskaming et de SudburyManitoulin-Parry Sound pour le NordEst et de la ville de Thunder Bay, du district de Kenora, du district de Rainy River ainsi que du district de Thunder Bay pour le Nord-Ouest. Le présent rapport effectuera un état de la situation pour chacune de ces huit régions, et ce afin d'identifier les besoins pressants de chacune d’entre elles et ainsi développer des pistes d’actions adaptées à ces besoins.

État des lieux pour le secteur des soins à domicile et en milieu communautiare dans le nord de l'Ontario - Réseau du mieux-être francophone du Nord de l'Ontario (2025)
Le Réseau a entrepris le travail de recenser les capacités actuelles du secteur des soins à domicile et en milieu communautaire dans le Nord de l’Ontario, et ce, afin de mieux appuyer les organismes de soins de santé et ainsi renforcer les capacités du secteur. En effet, cette étude permettra au Réseau de connaître les capacités actuelles en termes de professionnels de la santé qui parlent le français dans le Nord de l’Ontario, puis d’identifier les domaines et les régions où les disparités sont plus importantes. Ce rapport pourra servir de guide envers l’établissement des priorités et de stratégies régionales en matière de services en français pour le secteur des soins à domicile et en milieu communautaire. La majorité des données utilisées pour la réalisation de ce rapport sont tirées du rapport annuel 2022-2023 sur les services de santé en français envoyé au ministère de la Santé de l’Ontario et Santé Ontario, rapport qui est rempli annuellement par tous les fournisseurs de services de santé (FSS) qui ont une entente de responsabilisation avec Santé Ontario Nord. Les fournisseurs pour les populations autochtones sont toutefois exclus de cette étude. Afin d’analyser les capacités actuelles du système de santé dans le Nord de l’Ontario, le Réseau a choisi d’explorer cinq thématiques pour chacune des régions du Nord de l’Ontario. Ces cinq thématiques sont la capacité en ressources humaines en français, l’offre active, la capture de l’identité linguistique, la documentation et les communications ainsi que l’utilisation des tierces parties. L’exploration de ces thématiques permettra d'identifier les forces existantes dans le secteur des soins à domicile et en milieu communautaire et les domaines qui requièrent plus d'attention

Gabarit – Sondage d’expérience des francophones (questionnaire) - Réseau du mieux-être francophone du Nord de l'Ontario (2021)
Le Réseau du mieux-être francophone du Nord de l'Ontario a créé des sondages pour appuyer les fournisseurs de services de santé à capturer l’expérience de leur clientèle francophone. Un sondage est destiné aux résidents habitant dans les foyers de soins de longue durée et aux personnes aidantes alors que l’autre sondage est destiné à la clientèle utilisant les services des autres types de fournisseurs de services de santé tels que les hôpitaux, les centres de santé communautaire, les services de santé mentale et de toxicomanie ainsi que les soins à domicile et en milieu communautaire. Ces gabarits de sondages sont disponibles sur le site internet du Réseau.

Improving the Francophone Experience in Healthcare – Final Report - Réseau du mieux-être francophone du Nord de l'Ontario (2021)

PLAINTES et COMPLIMENTS par rapport aux SERVICES EN FRANÇAIS / COMPLAINTS and COMPLIMENTS Regarding FRENCH LANGUAGE SERVICES - Réseau du mieux-être francophone du Nord de l’Ontario (2021)
Le Réseau du mieux-être francophone du Nord de l’Ontario a créé un gabarit d’affiche que les fournisseurs de services de santé peuvent utiliser pour expliquer à leur clientèle le processus de partage de préoccupations et de compliments sur les services en français afin que les bénéficiaires puissent partager les bons coups et les points à améliorer en matière de services en français.

Recommandations de l’étude de besoins sur les foyers de soins de longue durée du Nord de l’Ontario - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)
Ce rapport a pour objectif de faire la mise à jour de recommandations tirées d’une étude réalisée par le Réseau du mieux-être francophone du Nord de l’Ontario (Réseau) en 2017. Les actions comprennent, entre autres, l’identification de foyers pour l’offre de services en français ainsi que l'accompagnement de foyers pour l'amélioration des services en français et le développement de stratégies pour mettre en œuvre des soins culturellement adaptés. Dans le cadre de ce rapport, nous avons souligné les thèmes qui ont été partagés avec nous ou dont nous avons pris connaissance par l’entremise de notre travail avec nos partenaires. Le but est de capter l’essence de la réalité de l’expérience des francophones résidant dans les foyers de soins de longue durée, ainsi que d’offrir des pistes d'actions qui nous permettront d’assurer une meilleure planification des services en français dans les foyers de soins de longue durée dans le Nord de l’Ontario.

Recommendations from the Northern Ontario Long-Term Care Homes Needs Study - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)
The purpose of this report is to provide an update on the recommendations from a study completed by the Réseau du mieux-être francophone du Nord de l’Ontario (Réseau) in 2017. The actions include identifying homes where French-language services could be offered, accompanying those homes where French-language services could be improved and developing strategies to implement culturally appropriate care. In the context of this report, we have identified themes that were shared with us or that we became aware of through working with our partners. The goal is to capture the essence of the real experience of Francophone residents in long-term care homes as well as offer courses of action which will allow us to ensure better planning of French language services in long-term care homes throughout Northern Ontario.

Concrétiser le modèle de soins de longue durée à l’intention des francophones et d'autres membres de groupes culturels et linguistiques minoritaires - Réseau franco-santé du Sud de l’Ontario et partenaires (2020)

The impact of dementia and language on hospitalizations: A retrospective cohort of long-term care residents - Riad, Karine; Webber, Colleen; Batista, Ricardo; Reaume, Michael; Rhodes, Emily; Knight, Braden; Prud’homme, Denis; Tanuseputro, Peter (BMC Geriatrics, 2020)
Background Hospitalizations carry considerable risks for frail, elderly patients; this is especially true for patients with dementia, who are more likely to experience delirium, falls, functional decline, iatrogenic complications, and infections when compared to their peers without dementia. Since up to two thirds of patients in long-term care (LTC) facilities have dementia, there is interest in identifying factors associated with transitions from LTC facilities to hospitals. The purpose of this study was to investigate the association between dementia status and incidence of hospitalization among residents in LTC facilities in Ontario, Canada, and to determine whether this association is modified by linguistic factors. Methods We used linked administrative databases to establish a prevalent cohort of 81,188 residents in 628 LTC facilities from April 1st 2014 to March 31, 2017. Diagnoses of dementia were identified with a previously validated algorithm; all other patient characteristics were obtained from in-person assessments. Residents’ primary language was coded as English or French; facility language (English or French) was determined using language designation status according to the French Language Services Act. We identified all hospitalizations within 3 months of the first assessment performed after April 1st 2014. We performed multivariate logistic regression analyses to determine the impact of dementia and resident language on the incidence of hospitalization; we also considered interactions between dementia and both resident language and resident-facility language discordance. Results The odds of hospitalization were 39% lower for residents with dementia compared to residents without dementia (OR 0.61, 95% CI 0.57–0.65). Francophones had lower odds of hospitalization than Anglophones, but this difference was not statistically significant (OR 0.91, 95% CI 0.81–1.03). However, Francophones without dementia were significantly less likely to be hospitalized compared to Anglophones without dementia (OR 0.71, 95% CI 0.53–0.94). Resident-facility language discordance did not significantly affect hospitalizations. Conclusions Residents in LTC facilities were generally less likely to be hospitalized if they had dementia, or if their primary language was French and they did not have dementia. These findings could be explained by differences in end-of-life care goals; however, they could also be the result of poor patient-provider communication.

Understanding patient barriers and enablers to accessing community resources: a qualitative study to inform navigation service delivery - Saluja, Kiran; Mahbub, Adiba; Gauthier, Alain P.; Lemonde, Manon; Timony, Patrick; Durand, François; Dahrouge, Simone (BMC Primary Care, 2025)
Abstract Background Individuals face multifaceted barriers to accessing community resources, which can significantly impact their ability to obtain necessary support and services. This study examines barriers and enablers to access community resources among primary care patients and explores the interplay between individual- and system-level factors that influence access to resources. Methods In this qualitative study, we conducted 32 semi-structured interviews with primary care patients who participated in a social prescribing trial that compared two navigation services: ARC (patient-centered longitudinal support) vs. Ontario-211 (free 24-hour helpline service) in two regions, Ottawa and Sudbury, in the province of Ontario, Canada. We conducted thematic data analysis with a deductive/inductive hybrid approach, employing Levesque’s theoretical framework for access to health that examines the various system and individual level factors influencing access to healthcare services. Findings At the system level, various systemic barriers encompassing broader organisational, structural, and policy-related elements influenced patients' access to community resources (outreach, availability, location, costs and accommodations for patient needs and preferences). These factors directly interacted with various patient-level factors (awareness of needs, ability to seek support, to reach resources and to pay for those, their physical and mental health, motivation, and confidence to engage in care) to determine access. Conclusions Our findings highlight individual- and system-level barriers and enablers for accessing community resources among socially complex primary care patients with multiple unmet needs. As governments and organizations in Canada are increasingly investing in community-based services to address adverse social determinants of health (SDH), an upstream approach that reduces both systemic and individual-level barriers to access is warranted. Language significantly influences access to services, particularly for linguistic minorities (see page 5 and 7)

Processus de développement d’une trousse d’accompagnement pour l’examen médical des nouveaux arrivants francophones : un exemple de coopération - Sanou, Boroma; Beaudoin, Monique; Gauthier, Alain P.; Chomienne, Marie-Hélène; Prud’homme, Denis; Kpazaï, Georges (Revue de la Diversité de la Recherche en Santé, 2020)
While over the half of Francophone immigrants living in Ontario come from Africa and the Caribbean, Canadian-trained health professionals are not sufficiently familiar with the health problems that newcomers may face. With this in mind, in a multi-disciplinary partnership, the Center for Rural and Northern Health Research, the Centre de santé communautaire du grand Sudbury, l’Institut du savoir Montfort, the School of Human Kinetics at Laurentian University, and a group of French-speaking immigrants from the City of Greater Sudbury, developed using a collaborative research approach, a newcomer’s medical examination toolkit for health professionals and social services. The toolkit development process involved several steps: 1) establishing a partnership between the above-mentioned organizations; 2) literature review to identify the most common health problems; 3) selection of the most common problems that are not necessarily those that health professionals encounter in everyday practice; 4) writing of draft versions with emphasis on some important aspects of the disease; 5) validation of the fact sheets by the partners; 6) the restitution of the final fact sheets (25 fact sheets including 3 on the general examination, 10 related to certain tropical diseases, 8 sheets related to the signs and symptoms most frequently encountered by health professionals and the other 4 on health care in Ontario); and 7) the development of a digital infograph to ensure greater visibility of the Toolkit for the medical examination of Francophone newcomers.

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Centre de recherche en santé dans les milieux ruraux et du nord, 2020)

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal, 2020)

Données sur les soins de longue durée en français-Équipe Santé Ontario du Grand Fleuve [infographie] - Santé Ontario; Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada (2022)

Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

Active offer of services in Canada’s official languages: development of a patient experience questionnaire - Sauvé-Schenk, Katrine; Pignac, Sarah; Kemenade, Solange; Savard, Sébastien; Prud'homme, Denis; Savard, Jacinthe (Journal of Communication in Healthcare, 2026)
ABSTRACT Background: In the bilingual Canadian context, the use of a preferred official language with healthcare providers is linked to optimized communication, respectful patient-centered care, improved safety and quality of services. This study aimed to develop and test a questionnaire that measures patients’ experience of how language was considered during an outpatient health encounter. Methods: French and English questions were drafted based on a literature review. Questionnaire content and flow were validated through focus groups with experts and service users. Question understanding and clarity was verified with cognitive interviews and pre-tests with diverse service users. The final questionnaire was pilot tested in three health organizations and temporal stability, and construct validity was verified. Results: Participants were nine anglophone and eleven francophone experts and service users for the focus groups, six anglophone and six francophone service users for the cognitive interviews, eleven anglophone and ten francophone service users for the pre-test. The resulting questionnaire has 31 experience-related questions organized under six themes: arrival/greeting, interpretation and translation services, language of health services, relationship with healthcare providers, visibility of official languages and follow-up. The questionnaire is completed online in French or English. The questionnaire was pilot tested with 199 participants in three sites. Temporal stability was moderate to good. Initial evidence of construct validity was demonstrated, suggesting that the questionnaire is adequate to evaluate patient experience. Conclusion: This questionnaire is the first known bilingual patient-experience tool, focused on the active offer of services in official languages during outpatient healthcare encounters, with preliminary validation.

Implementing Active Offer of Services in Both Official Languages in a Hospital Setting in Ontario - Sauvé-Schenk, Katrine; Savard, Jacinthe; Durand, François (Healthcare Policy, 2024)
Providing services in a patient's preferred language is linked to safe and quality care. This paper presents the process and outcomes of implementing practices of active offer (AO) of French-language services in a hospital setting in a region of Ontario with a low density of francophones. Participating unit managers and site coordinators selected AO practices and carried out an implementation plan. The implementation's success was linked to the support received from higher management and site coordinators. Challenges included the managers' rival priorities and perceived language priorities. This process could be applied to meet the needs of other language communities.

Conditions gagnantes pour une offre active de services en français efficace dans un milieu à faible densité de francophones : résultats d’une étude pilote. Rapport sommaire présenté à la Société Santé en français - Sauvé-Schenk, Katrine; Savard, Jacinthe; Prud’homme, Denis; Durand (Chiocchio), F.; Delluc, C. (Institut du savoir Montfort et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Évaluation de la mise en œuvre de services en français en contexte minoritaire : développement d’un questionnaire sur l’expérience des usagers - Sauvé-Schenk, Katrine; Savard, Jacinthe; Savard, Sébastien; Prud’homme, Denis; van Kemenade, Solange; Le Callonnec, Lucie; Pignac, Sarah (2022)

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.

Improving the active offer of french language services - Savard, Jacinthe; Sauvé-Schenk, Katrine (Société Santé en français, 2020)

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)
Résumé Contexte. Des études menées pendant la pandémie de COVID-19 soulignent que le confinement a réduit l’accès aux services et accru les responsabilités et l’isolement des proches aidants. Objectif. Cette étude examine les répercussions à long terme chez 83 proches aidants de personnes âgées provenant de quatre provinces canadiennes. Méthodes. Les participants ont rempli un questionnaire en ligne entre octobre 2021 et février 2022, puis à nouveau six mois plus tard, sur l’aide fournie, le soutien reçu, la langue des services et le bien-être psychologique. De plus, huit aidants ont participé à une entrevue qualitative. Résultats. La plupart des services d’aide à domicile ont été maintenus pendant la pandémie, certains avec un personnel réduit, à l’exception des services de répit et de transport. Les aidants ont accru leur aide pendant les confinements, et cette implication accrue s’est poursuivie en 2022. Ils ont perçu un impact négatif de la pandémie sur leur santé et celle de la personne aidée. Les participants issus de communautés linguistiques minoritaires officielles ont décrit des difficultés supplémentaires pour accéder aux services dans leur langue préférée. Discussion. Une meilleure reconnaissance des besoins des aidants contribuera à soutenir leur rôle en tant que partenaires au sein des organismes de santé. Abstract Background. Studies conducted during the COVID-19 pandemic highlighted that confinement reduced access to services and increased caregivers’ responsibilities and isolation. Objectives. This study examines the longer-term impacts among 83 unpaid caregivers of older adults from four Canadian provinces. Methods. Participants completed an online questionnaire between October 2021 and February 2022, and again 6 months later, on the assistance provided, support received, language of services, and psychological well-being. Additionally, eight caregivers participated in a qualitative interview. Findings. Most home support services were maintained during the pandemic – some with restricted staffing – except for respite and transportation services. Caregivers increased their assistance during the lockdowns, and this higher involvement persisted in 2022. They perceived a negative impact of the pandemic on their health and that of the care recipient. Participants from official language minority communities described additional challenges accessing services in their preferred language. Discussion. Greater recognition of caregivers’ needs will help support their role as partners within health organizations.

Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2021)
Tous les organismes qui souhaitent offrir des services en français n’ont pas nécessairement les ressources nécessaires pour le faire. Les points de service satellites francophones constituent des ententes formelles par lesquelles des intervenant·es ou des professionnel·les de services sociaux et de santé d’un organisme offrent des services dans les locaux d’un autre organisme, dans le but de mieux servir les personnes âgées francophones. Les services offerts varient selon les besoins décelés par l’organisme hôte du service satellite, ainsi que les ressources disponibles (financières, main-d’œuvre) de la part de l’organisme fournissant le service.

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2021)
Le quartier de Vanier, situé à l’est de la rivière Rideau, dans la ville d’Ottawa, abrite un grand nombre des personnes aînées francophones. Toutefois, une carence de services offerts en français et des conditions socioéconomiques précaires constituent des réalités qui tendent à vulnérabiliser la population. Les Lunchs-causeries du CSC Vanier Les lunchs-causeries ont vu le jour en 2009 grâce à une collaboration entre divers acteurs du milieu. Il s'agit de rencontres mensuelles qui visaient à briser l’isolement ainsi qu’à informer et outiller les personnes aînées de deux immeubles subventionnés pour personnes âgées dans le quartier Vanier, en vue d’accroître leur qualité de vie. Ils constituaient une occasion de construire un lien de confiance entre la personne aînée et l’intervenant·e du CSC Vanier Divers défis, dont ceux de son financement, font qu'en 2025, la pratique n'était plus mise en oeuvre.

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2021)
Ce programme, financé par Santé publique Ottawa, permettait le déploiement d’une infirmière de cet organisme dans le Centre de services communautaires (CSC) Vanier, qui dessert une communauté d'ainés majoritairement francophone. Son rôle était d’identifier les besoins des personnes aînées et de faire l’aiguillage de ces personnes vers les services dont elles avaient besoin. Tout comme l’ont fait les intervenant·es psychosociaux du CSC Vanier, l’infirmière de Santé publique Ottawa a pu utiliser la porte des Lunchs-causeries (voir pratique #12) pour rejoindre les résident·es dans leur milieu de vie et aborder leurs préoccupations de santé. L’infirmière pouvait ainsi aider à la gestion des médicaments et faire de l’aiguillage vers les services de santé de niveau de soins appropriés, dans le but de réduire les visites non nécessaires aux urgences des hôpitaux. Divers défis, dont ceux de son financement, que la pratique n'a pas pu être perrénisée.

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2021)
Les foires d’information sont des évènements annuels qui visent à nformer les personnes aînées francophones dans leur langue, sur divers sujets qui peuvent avoir une incidence sur leur qualité de vie. De plus, les foires d’information constituent des plateformes de réseautage et une occasion de créer ou de renouveler des partenariats pour les organisations participantes. Les foires d’information permettent aux aînés francophones de mieux connaître les services disponibles en français, et aux organisations, de mieux connaître les besoins de la population aînée francophone.

Pratique # 3: Le Pavillon Omer Deslauriers : une unité francophone au Foyer Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2021)
Cette initiative de créer une aile francophone, le Pavillon Omer Deslauriers, au sein de Bendale Acres, un foyer de soins majoritairement anglophone, visait à offrir des soins de longue durée dans la langue officielle de préférence des résident·es. Ainsi, le Pavillon permet aux aîné·es francophones d’avoir accès à des soins de longue durée et de fin de vie en français, grâce à un personnel majoritairement bilingue.

Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, - Savard, Sébastien; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; de Moissac, Danielle; Durand, François; Dupuis-Blanchard, Suzanne (2024)

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Contributions d’OZi à l’état des lieux des services de santé en français en Ontario. - Scullion, David; Taillon, Myriam; Ranger, Marie-Christine; Glaude, Normand; Desaulniers, Jacinthe (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Entre 2017 et 2020, l’organisme OZi a effectué la collecte et l’analyse de données sur les services de santé en français à l’échelle de la province, dans le cadre de la Loi sur les services en français de l’Ontario. Les résultats de cette recherche descriptive et exploratoire portent sur la répartition géographique de l’offre des services de santé en français, le continuum de soins, les exigences de la désignation et les ressources humaines possédant des capacités linguistiques en français. Ces résultats permettent de dresser l’état des lieux des services de santé en français en Ontario, en mettant en lumière les points forts comme les lacunes des services de santé en français. Les résultats sont discutés sous l’angle de l’accès et la planification des services de santé en français ainsi que celui de la performance de la désignation. Mots-clés : santé, offre active, Ontario, désignation des fournisseurs de santé, continuum de soins

Patient-physician language concordance and quality and safety outcomes among frail home care recipients admitted to hospital in Ontario, Canada - Seale, Emily; Reaume, Michael; Batista, Ricardo; Eddeen, Anan. Bader; Roberts, Rihannon; Rhodes, Emily; McIsaac, Daniel. I.; Kendall, Claire. E.; Sood, Manish. M.; Prud'homme, Denis; Tanuseputro, Peter (Canadian Medical Association Journal, 2022)
Background: When patients and physicians speak the same language, it may improve the quality and safety of care delivered. We sought to determine whether patient–physician language concordance is associated with in-hospital and postdischarge outcomes among home care recipients who were admitted to hospital. Methods: We conducted a population-based study of a retrospective cohort of 189 690 home care recipients who were admitted to hospital in Ontario, Canada, between 2010 and 2018. We defined patient language (obtained from home care assessments) as English (Anglophone), French (Francophone) or other (allophone). We obtained physician language from the College of Physicians and Surgeons of Ontario. We defined hospital admissions as language concordant when patients received more than 50% of their care from physicians who spoke the patients’ primary language. We identified in-hospital (adverse events, length of stay, death) and post-discharge outcomes (emergency department visits, readmissions, death within 30 days of discharge). We used regression analyses to estimate the adjusted rate of mean and the adjusted odds ratio (OR) of each outcome, stratified by patient language, to assess the impact of language-concordant care within each linguistic group. Results: Allophone patients who received language-concordant care had lower risk of adverse events (adjusted OR 0.25, 95% confidence interval [CI] 0.15–0.43) and in-hospital death (adjusted OR 0.44, 95% CI 0.29–0.66), as well as shorter stays in hospital (adjusted rate of mean 0.74, 95% CI 0.66–0.83) than allophone patients who received language-discordant care. Results were similar for Francophone patients, although the magnitude of the effect was smaller than for allophone patients. Language concordance or discordance of the hospital admission was not associated with significant differences in postdischarge outcomes.

Soutien aux proches-aidants francophones en situation minoritaire dans le contexte nordique : la contribution de la dynamique communautaire partenariale du Nord de l’Ontario au vieillissement à domicile - Siméon, Frantz; Célestin, Guison; Couturier, Yves; Larocque, Sylvie; Timony, Patrick (2025)
Faits saillants Cette recherche confirme et soutient : 1. Le fait que la proche-aidance se conjugue presque exclusivement au féminin. Deux facteurs expliquent ce fait de notre point de vue : (1) les femmes sont plus nombreuses au grand âge, donc sont statistiquement plus représentées dans le rôle que les hommes, (2) la socialisation des femmes au rôle du prendre soin et son intégration par celles-ci comme allant de soi témoigne d’une légitimation à priori de l’idée que le poids de l’aidance relève naturellement de la femme. 2. Que l’aidance en contexte minoritaire francophone est un travail qui va au-delà du temps plein ; la personne proche-aidante, indépendamment du degré de perte d’autonomie de la personne aidée, doit être présente 24 h/24, 7 j/7. Elle exige à la fois de l’intervention directe (prendre soin de son proche, l’accompagner, le soutenir…) et de l’intervention indirecte (assumer la coordination des services, plaider pour les services en français…). 3. Qu’entre le discours politique sur le soutien à domicile et la réalité des proches-aidantes en contexte francophone minoritaire, il y a un écart énorme à combler par des mesures concrètes de soutien et d’accompagnement. Ces mesures nécessitent d’importants investissements, notamment dans le financement des organismes de proximité qui constituent un filet de sécurité de première ligne pour un vieillissement à domicile à la hauteur des attentes des aînés francophones.

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)

Diversité linguistique au Canada, 2021 : tableau de bord interactif - Statistique Canada (2021)

How poverty rates differed by language in Quebec, New Brunswick and Ontario in 2021 - Statistique Canada (2026)

Language diversity in Canada, 2021: Interactive dashboard. - Statistique Canada (2026)

Poverty rate of the bilingual population in Quebec, New Brunswick and Ontario in 2021 - Statistique Canada (2026)

Taux de pauvreté au sein de la population bilingue du Québec, du Nouveau-Brunswick et de l’Ontario, 2021 - Statistique Canada (2021)

Variations dans les taux de pauvreté selon la langue au Québec, au Nouveau-Brunswick et en Ontario - Statistique Canada (2021)

Enjeux et complexité de la démence en milieu rural francophone : regards sur les réalités familiales [mémoire de maîtrise, Université d'Ottawa] - Sullivan, Cassidy (Université d'Ottawa, 2020)
Les personnes aînées se retrouvent parmi les groupes les plus susceptibles d’être diagnostiqués d’une maladie cognitive, telle qu’une démence. La réception du diagnostic est un événement bouleversant pour toutes les personnes impliquées, et plus particulièrement pour les familles. Dans la région d’Ottawa, il existe une variété de ressources pour soutenir les personnes atteintes d’une démence ainsi que leurs proches. Or, la littérature disponible indique que les personnes francophones vivant dans un milieu rural ne vivent pas la même réalité (Forgues, Doucet et Guignard (2011). Bien que les impacts de la démence sur les relations familiales pourraient varier d’un endroit à un autre, l’emplacement et la disponibilité des services francophones jouent également un rôle important dans le parcours de ces personnes. Ces facteurs nous invitent à poser la question suivante : Quels sont les impacts de la démence sur la dynamique familiale et l’accès aux services francophones des personnes vivant dans un milieu rural ? À partir de la perspective d’intervenantes sociales, l’étude a permis : 1) d’explorer les réalités et enjeux vécus par les familles lors de la réception d’un diagnostic de démence, comme la maladie d’Alzheimer, chez un proche âgé vivant dans un contexte rural francophone ; 2) d’examiner les défis d’accès aux services rencontrés par les aidants familiaux, et finalement ; 3) de comprendre les réalités des familles lors de la progression de la maladie. Cette recherche a été menée dans les Comtés unis de Prescott-Russell, une région bilingue de l’est de l’Ontario. Dans cette étude, nous avons identifiés le vécu des familles suite à la réception d’un diagnostic de démence, ainsi que les ressources disponibles pour les personnes de cette région qui sont touchées par la maladie. En ce qui trait au cadre conceptuelle et théorique choisi pour cette étude, nous avons optés pour l’épreuve relationnelle et l’approche écosystémique pour analyser nos thèmes. Sur le plan méthodologique et en se basant sur des entrevues semi-dirigées, cette étude a nécessité la participation de trois intervenantes sociales œuvrant auprès des familles ayant un proche atteint d’une démence, et ce, dans la région de Prescott-Russell. Il ressort principalement des résultats de cette étude que les enjeux observés par les intervenantes sur la gestion de la démence en milieu rural et l’accès aux services sont lié à la navigation entre les services, l’éducation sur la démence et l’optimisation des services de soutien. Ces dernières constatent des points à améliorer en ce qui concerne le discours social sur le vieillissement ainsi que le manque de financement pour l’augmentation de la visibilité et de l’accessibilité des services francophones. Mots clés : Personne aînée, maladie d’Alzheimer, ruralité, francophonie, accessibilité, services adaptés, dynamique familiale

Recruiting service providers with French proficiency: Tips and strategies - The Knowledge Institute on Child and Youth Mental Health and Addictions (2023)
This report is designed as a resource to support the "Kids Come First Health Team" in developing a strategy for recruiting, retaining and training human resources in Ontario’s Champlain health region. The report has been prepared by the Knowledge Institute on Child and Youth Mental Health and Addictions (the Knowledge Institute). The Knowledge Institute builds connections, shares knowledge and draws on expertise to enhance the skills of direct service providers and agencies across Ontario in order to strengthen Ontario’s mental health programs and services for all children, young people, families and caregivers. We wanted to discover what organizations are doing — particularly organizations in the health sector — to recruit service providers with French proficiency. We also wanted to learn about evidence-based practices for recruitment from the literature. The strategies and guiding principles provided in this resource were derived from an environmental scan that included a rapid, nonsystematic literature review. As well, we consulted with key stakeholders and leaders in the field who have direct experience with recruiting service providers with French proficiency.

Des services de santé dans ma langue, un “horizon d’attente” : Programme de santé mentale de Montfort et parcours psychiatriques. - Thifault, Marie-Claude (Le moment Monfort dans la francophonie canadienne, 2024)

Dérives : une histoire sensible des parcours psychiatriques en Ontario français - Thifault, Marie-Claude; LeBel, Marie (Les Presses de l'Université d'Ottawa, 2021)

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society / Minorités linguistiques et société, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal / Revue de la diversité de la recherche en santé, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

Reporting on knowledge, attitudes, and behaviours of pharmacists regarding the active offer of French language health services in Ontario: A quantitative survey study - Timony, Patrick; Leone, Arielle; Caron, Carolanne; Giguère, Pierre; Thabet, Pierre; Gauthier, Alain; Waite, Nancy M.; Landry, Christine (Canadian Pharmacists Journal / Revue des Pharmaciens du Canada, 2025)
Background: Patient–provider language discordances can negatively affect the availability, accessibility, acceptability, and quality (AAAQ) of pharmacy services as described by the AAAQ framework. With nearly 600,000 residents of Ontario identifying French as their mother tongue, the active offer (AO) of French language pharmacy services should be provided, yet little is known about pharmacists’ familiarity and use of AO. Methods: Ontario pharmacists completed an online survey measuring their knowledge, attitudes, and behaviours (KAB) regarding the AO for French language services (FLS). Demographics, including ability to converse in French, were collected. KAB AO scores were calculated and compared using descriptive and inferential statistics. Results: A total of 360 pharmacists completed the survey. The majority (65.1%) practiced in a primary care setting, 21.1% spoke French, and 71.8% lived in an area where less than 10% of the population were Francophone. Overall, AO scores were highest for attitude (3.8/5) and lowest for behaviours (2/5) and knowledge (1.8/5). Most pharmacists (62.8%) indicated an interest in AO training. Discussion: Gaps in KAB regarding AO for FLS by Ontario pharmacists resemble those observed throughout the health care system. Further training is suggested to address the lack of knowledge regarding AO, particularly its proactive nature, as well as strategies for its implementation. Conclusion: Although most participating pharmacists demonstrated gaps in AO knowledge and behaviour, many had favourable attitudes toward the importance of AO in the pharmacy setting and agreed that further training would be needed to improve their KAB. Further, the AO can address all 4 elements of the AAAQ framework.

Adopting a lay navigator training programme in primary care - Toal-Sullivan, Darene; Lemonde, Manon; Gauthier, Alain P.; Dahrouge, Simone (Health Education Journal, 2021)
Introduction: There is growing interest in the role and use of patient navigators within the health care system. Currently, qualifications and training expectations documented in the literature vary tremendously depending on context and patient population. This paper details the theoretical and pedagogical principles used to develop, implement and evaluate a training programme for lay patient navigators working in a primary care setting. Methods: The planning process involved (a) conducting an educational needs assessment, (b) identifying the theory underpinning the curriculum, (c) developing learning objectives and teaching strategies, (d) formulating evaluation methods, (e) implementing the programme and (f) refining the curriculum based on evaluation feedback and lessons learned. The training programme was first implemented in May 2017 and has evolved over the past 3 years based on our observations and feedback from the programme participants. Results: The training programme involves a total of 25 hours of online and face-to-face education sessions, and ongoing community mentorship from experienced navigators. All training components are rooted in theoretical principles and proven pedagogical approaches. The knowledge, skills and abilities acquired are also tied to core competencies of the role of lay patient navigator. Conclusion: The development of this lay navigator training programme was carefully designed with evidence-based competencies and practical realities to ensure rigour in preparing and supporting navigators’ work in primary care settings.

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2025)
Le Centre francophone du Grand Toronto (CFGT ou le Centre) est la porte d’entrée pour les francophones qui vivent à Toronto ou qui s’y installent. Le Centre est un organisme sans but lucratif qui compte plusieurs points se services et offre une gamme diversifiée de services communautaires de santé, de services sociaux et d’accès au logement à l’ensemble de la communauté francophone du Grand Toronto. L’objectif du projet était la création d’un système d’enregistrement des usagers et usagères du Centre qui facilite l’accès à tous les services en une seule demande grâce à un formulaire en ligne ; l’uniformisation des pratiques d’accueil et des informations demandées aux clients, la centralisation de l’information sociodémographique pour mieux coordonner la collecte des données et l’aiguillage vers les services appropriés pour la clientèle. L’accueil centralisé facilite la collecte des données sociodémographiques des usager·ères (évite les répétitions), permet un aiguillage plus rapide et efficace, tout en répondant mieux aux demandes de bailleurs de fonds. Le système permet de centraliser l’information sur les services sollicités et leur provenance parmi plusieurs points de services, informations qui peuvent être utilisées pour la conception et la mise en place de nouveaux programmes.

Expériences de soins à domicile et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; Bouchard, Louise (Université d'Ottawa, 2026)
La présente étude visait à comprendre l’expérience des soins à domicile aux personnes aînées francophones en Ontario et l’impact des barrières linguistiques dans ce secteur, à partir des perspectives des gestionnaires, des intervenant·es, ainsi que des bénéficiaires et de leurs proches aidant·es. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des fournisseurs de services. Ce rapport de recherche intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences de soins à domicile et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; Bouchard, Louise (Université d'Ottawa, 2026)
La présente étude visait à comprendre l’expérience des soins à domicile aux personnes aînées francophones en Ontario et l’impact des barrières linguistiques dans ce secteur, à partir des perspectives des gestionnaires, des intervenant·es, ainsi que des bénéficiaires et de leurs proches aidant·es. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des fournisseurs de services. Ce rapport de synthèse décrit les principaux constats de l'étude, accompagnés de quelques citations de participants.

Home Care Experiences and Language Challenges in Ontario: Perspectives of Francophone Seniors, Family Caregivers, Frontline Care Providers, and Managers. Summary report - van Kemenade, Solange; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; Bouchard, Louise (Université d'Ottawa, 2026)
La présente étude visait à comprendre l’expérience des soins à domicile aux personnes aînées francophones en Ontario et l’impact des barrières linguistiques dans ce secteur, à partir des perspectives des gestionnaires, des intervenant·es, ainsi que des bénéficiaires et de leurs proches aidant·es. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des fournisseurs de services. Ce rapport de synthèse décrit les principaux constats de l'étude, accompagnés de quelques citations de participants.

Les expériences de patients francophones qui se présentent fréquemment à l'urgence pour des raison de santé mentale - Vandyk, Amanda; Lightfoot, Sophie; Levesque, Kristine; Domecq, Marie-Cécile.; Jacob, Jean Daniel (Recherche en soins infirmiers, 2022)
Introduction: Language and communication are pivotal to the safe care and management of people with mental health disorders, particularly when these patients are linguistic minorities. Objectives/method: To explore these experiences within linguistic minority populations by completing a literature review and qualitative interviews. Interviews were conducted in Ottawa, Canada, with francophone patients. The studies included in the review represented the international literature on linguistic minorities in general. Results: Overall, the experiences described in the published articles were similar to the participants' own experiences, suggesting that barriers to care exist even in settings mandated to provide services in both official languages. Discussion/conclusion: There are many barriers to the provision of mental health care services, regardless of the dominant language. However, we identified an internalized sense of responsibility felt by linguistic minority patients, who feel compelled to compensate for or fill in the language gaps of providers. Keywords: health services accessibility; language; mental health; qualitative research; rapid review.